Keeping Kenya Learning: The importance of caregiver engagement in supporting learning beyond the classroom - Kimathi, Deborah; El-Serafy, Yomna; Plaut, Daniel; Kaye, Tom (EdTech Hub, 2021)
Since the Covid-19 pandemic began, parents, teachers, students and policymakers have been exploring how to support students to learn at home. The emphasis on education at home has made evident the need to better equip caregivers to support their children’s learning.  The Keep Kenya Learning (KKL) initiative is helping parents and caregivers build their capacity and confidence to support learning…
Keywords: _EdTechHub_Output

EdTech in Kenya: A Rapid Scan - Otieno, J.; Taddese, A. (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private-sector partnerships, and the digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive; however, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Kenya. This report was originally written in June 2020. It is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Kenya; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

Kenya: Off-grid Solar Access Project for Underserved Counties - World Bank (2020)
Kenya: Off-grid Solar Access Project for Underserved Counties

The Use of Technology to Promote Equity and Inclusion in Education in North and Northeast Kenya - Otieno, Jennifer; Kaye, Tom; Mbugua, Wanjiku (EdTech Hub, 2023)
Kenya has been lauded as having one of the most progressive and effective education systems in Africa. Significant investments in education funding, innovative technology-enabled approaches to improve teaching and learning, and committed leadership make Kenya an example for neighbours and others across the world. However, at a sub-national level, significant variances in education access and quality arise. While many improvements have been made to participation, quality, equity, and inclusion in education in Kenya, there are persistent disparities in access and outcomes for rural learners, girls, learners with disabilities, and other vulnerable populations. The North and Northeastern (N/NE) counties of Kenya are where some of the greatest disparities exist. Our research examines the context of N/NE Kenya to understand why these disparities exist, and how technology can play a role in increasing equity and inclusion in education in the region. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Telephone Survey: Caregivers' and Learners' Perspectives on SMS for Education in Kenya - Myers, Christina; Jordan, Katy; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia; Zhao, Annette (EdTech Hub, 2022)
This document presents the structure and questions used for a telephone survey which was undertaken with a sample of learners who use the M-Shule platform and their caregivers, in Kenya, during July and August 2022. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech and the COVID-19 response: A case study of Kenya - Ngware, Moses; Ochieng, Vollan (EdTech Hub, 2020)
Keywords: Kenya; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Kenya: extreme inequality in numbers - Oxfam (Oxfam International, 2020)

Kenya GPE COVID-19 Learning Continuity in Basic Education: Stakeholder Engagement Plan - Ministry of Education, Kenya (2020)

Kenya Basic Education COVID-19 Emergency Response Plan - State Department of Early Learning and Basic Education, Kenya (2020)

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Parent and Caregiver Engagement in Kenya: Gaps, opportunities, and emerging questions for future research - Flam, Rebekka; Honda, Delanie; Ramesh Vasudevan, Sharanya; Mbugua, Wanjiku (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Kenya Public Expenditure Review 2020: Options for Fiscal Consolidation after the COVID-19 Crisis - World Bank (World Bank, 2020)
The objective of this public expenditure review (PER) is to provide the government with options for fiscal consolidation and support macroeconomic stability in the medium-term. This PER addresses the broad topic of expenditure efficiency and examines options for expenditure rationalization to help return Kenya’s fiscal accounts to a prudent trajectory in the medium-term. The PER is being undertaken as a programmatic analytical product with two modules. The first module focuses on identifying options for expenditure rationalization and measures to strengthen within-year expenditure control for better expenditure management. The second module to be delivered in FY21 will focus on efficiency, effectiveness, and equity of spending within public services delivery sectors of education, health, and disaster risk financing. The report builds upon several other Bank-led reports that contribute to the discussion around improving public expenditure and strengthening expenditure controls in Kenya. It complements an ongoing governance for enabling service delivery and public investments in Kenya (GESDeK) project, which is at the forefront in supporting numerous reforms highlighted in this PER to improve efficiency in spending and strengthen expenditure controls. The report is organized as follows: chapter one contains the macro context, trends, and composition of spending, overall balance and debt. Chapter two contains the fiscal and debt sustainability analysis while chapter three presents options for expenditure rationalization in Kenya. Chapter four ties it all together with fiscal savings and policy recommendations.
Keywords: Debt Sustainability; Expenditure Control System; Fiscal Sustainability; Fiscal Trends; Public Debt; Public Expenditure; Public Investment Management; Public Procurement; Public Wage Bill; Revenue

Keep Kenya Learning: Helping Caregivers Support Learning at Home Sprint 1 - Mbatha, FaithMbithe; Crook, Rebecca; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org Our research indicates that guidance and resources are necessary but insufficient in equipping caregivers to support their children’s learning. In Sprint 1, caregiver confidence and community emerged as important enablers of home learning. In our interviews, caregivers communicated how they felt limited by their lack of or outdated education. Global interventions indicate that reinforcing a sense of community for caregivers and enabling them to learn from modelling by trusted messengers are pathways to building greater engagement. Caregivers in both rural and urban communities expressed a willingness to engage with SMS (short message service) and online educational resources. However, it is clear that resource design must be: Accessible and understandable Credible and trusted Relevant and actionable.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted; ⛔ No INSPIRE recid found

Cost-effectiveness of digital personalised learning: Three interventions from Kenya - Anonymised for Peer Review (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

The ICT Landscape in Northern Kenya: Challenges & Opportunities - Mugendi, Jacob; Valbuena, Gustavo (Engineering For Change, 2020)
EDITORIAL TEAM: Carolina Rojas, E4C Expert Fellow; Mariela Machado, E4C Program Manager; Grace Burleson, E4C Research Manager DISCLAIMER: Any views and/or opinions expressed in this post by individual authors or contributors are their personal views and/or opinions and do not necessarily reflect the views and/or opinions of Huawei Technologies or iGov Africa. Click here to view the full report. The northern region of Kenya, which is arid and semi-arid in nature, forms...

Balloons to Deliver Emergency Internet Across Kenya - Alison, Buckholtz (2020)
Telkom Kenya-Loon partnership will result in country-wide 4G connectivity during pandemic, boosting government services.

Liquid Telecom Kenya (Liquid telecom, 2020)
Liquid Telecom in Kenya is a full-service data communications carrier offering a host of services including IP, broadband transport, infrastructure services and co-location services.

Reform Policy to Boost Kenya’s Mobile Connectivity Says GSMA - GSMA (2020)
48 Per Cent of the Population of Kenya Remains Unconnected to Mobile Networks   Nairobi: Kenya is making excellent progress to achieve its target of universal broadband coverage by 2030 and there is an opportunity for the government to accelerate the country’s digital transformation with more supportive policies. This was the key finding of a […]

Digital 2020: Kenya - DataReportal (2020)
All the data, statistics, and trends you need to understand digital use in Kenya in 2020, including the latest reported figures for the number of internet users, social media users, and mobile connections, and key indicators for ecommerce use.
Keywords: ___working_potential_duplicate

Randomised Controlled Trial Protocol: Digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms - Major, Louis; Daltry, Rebecca; Otieno, Mary; Otieno, Kevin; Zhao, Annette; Hinks, Jessica; Sun, Chen; Friedburg, Aidan (EdTech Hub, 2023)
This protocol provides a detailed overview of a cluster-randomised controlled trial (RCT) being undertaken in pre-primary schools in Kenya. The RCT seeks to rigorously investigate the impact of a classroom-integrated digital personalised learning (DPL) tool on early grade numeracy and literacy learning outcomes. The protocol is being disseminated prior to endline data analysis to promote transparency and a comprehensive understanding of the RCT approach and design. This protocol was originally published in October 2023. This is an updated version where we have a) clarified that the sample size stated in Sections 2 and 2.2 is the 'pre-attrition' sample; and b) added a paragraph to Section 2.4.1 to provide further clarification regarding the use of code-switching. No changes to the analytical approach have been made. Keywords: digital personalised learning; DPL; Randomised controlled trial; RCT; research methodology; learning outcomes; Kenya An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

The Power of Girls' Reading Camps: Exploring the impact of radio lessons, peer learning and targeted paper-based resources on girls’ remote learning in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Njeri, M.E.; Naylor, Ruth; Page, Ella; Riggall, Anna (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

The effect of internet services on child education outcomes: evidence from poa! Internet in Kenya - Okyere, Charles Yaw (Journal of Development Effectiveness, 2022)
In 2016-2018 poa! Internet, a private internet service provider, distributed free internet services across schools in Nairobi, Kenya. Using inverse probability weighting (IPW) method, the study finds that the intervention significantly increases students’ internet use and training, receipt of information on educational content, and participation in information and communication technologies (ICTs) education programmes. However, the study does not find evidence that internet services increase school attendance. The results suggest that facilitating access to internet services in schools can significantly increase child computer and internet skills and training in developing countries, even if those investments have limited gains on school attendance.
Keywords: Internet services; Kenya; education; gender; quasi-experimental design

Raising Readers: Can mobile technology enable Kenyan schools to improve parent and carer engagement in reading with their children? - Nicolai, Susan; Khan, Amina; Kartha, Ashwati; Bapna, Akanksha; Kamninga, Tony (EdTech Hub, 2023)
Deploying design-based, mixed-methods research, the study Raising Readers (Phase 1) explores how technology can be best used to strengthen parent and carer engagement with children’s reading in Kenya. In close collaboration with Worldreader, a digital reading organisation, five co-designed modalities (parental training, feedback loops, nudges/messaging, incentives, and reading celebrations) were tested in 14 schools across Nairobi and Kiambu counties over 12 weeks in 2022. The intervention helped to assess the potential of the different modalities in facilitating parental/carer engagement around children’s reading using the BookSmart app. As measured by average reading time, intervention groups showed higher engagement using BookSmart than the control group. ‘Incentives’ led with 39 hours 29 minutes average reading time per school over 12 weeks, followed by ‘reading celebrations’ with 24 hours 13 minutes. ‘Feedback loops’ and ‘training’ had comparable levels (10 hours, 28 minutes, and 9 hours, 27 minutes per school, respectively). ‘Messaging / nudges’ had the lowest engagement (5 hours 57 minutes versus 3 hours 2 minutes in the control group). Parental/carer knowledge, attitudes, and practices supporting their child's reading improved with the interventions. Findings of Phase 1 were used to inform the design of Phase 2. Keywords: Education, app, reading, school, child, Kenya An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Effect of Covid-19 Pandemic on the Education System in Kenya - Kathula, Domeniter Naomi (Journal of Education, 2020)
Education is an integral part of human society, its importance in life cannot be ignored as lack of education gives birth to numerous social problems like poor health, internal conflict, poor living standards and many more, education helps people to find a better solution to their problems. Education lets people realize the true value of contribution and help become the backbone of the society. Innovation and creativity can only occur when people are skilled enough to know how to operate with different technologies. Since the first case of the novel coronavirus (COVID-19) was announced in Kenya, many aspects of society and the education sector have been dramatically affected. On March 15th 2020, the Kenyan government closed all learning institutions countrywide to contain the spread of the virus. As the numbers of those infected by coronavirus rose to over 8,000, the ministry of education announced on July 7th that, the 2020 school calendar year will be considered lost due to COVID-19 restrictions. The purpose of this study was therefore to determine the effect of Covid-19 pandemic on the education systems in Kenya. The study was anchored on Classical Liberal Theory of Equal Opportunities. Mixed method design which involved a combination of both quantitative and qualitative approaches was adopted. In?quantitative the study used a survey research design, specifically the study adopted a cross-sectional survey research design. Cross-sectional survey design involves collecting data from a large group of people of different stages of growth at one point in time. The target population for this study included teachers, students and parents. The sample size for the study comprised of 100 teachers, 25 parents and 100 students who were purposively selected across the country. This study used both questionnaire and interview guide to collect primary data. The questionnaires were served to teachers and students online using Google forms while interview guide was administered to the parents using online Google forms as well. The quantitative data collected was analyzed using SPSS. Quantitative analysis involved the use of descriptive analysis, while qualitative data was analyzed using content analysis. The results were presented on tables. The findings revealed that Covid-19 had seriously affected learning among students in Kenya. The study found that the effects of Covid-19 were so severe that some teachers and parents lost their jobs or source of livelihoods. Most of the students were not able to access online learning due to lack of electricity, lack of learning materials and some were forced to relocate to the country side. The study hence concluded that as a result of the challenges presented by the coronavirus and the likely impact of future pandemics the government’s ability to ensure continuation of learning will depend on the ability to swiftly harness available technology, provide adequate infrastructure and mobilize stakeholders to prepare alternative learning programmes. The study concludes that as a result of the emergence of Covid-19 pandemic, teaching and learning activities in all learning institutions in Kenya just like other parts of the world have severely been disrupted. The worst hit learners are the primary and secondary school candidates who should sit for their national examinations at the end of 2020. Based on the conclusion the study recommended that there is need for the government through the ministry of education together with all the stakeholders in education sector in Kenya to navigate through challenges presented by Covid-19 to ensure continued access to provision of quality, equitable and inclusive education during and after the pandemic. Effective implementation of the proposed interventions by education managers and stakeholders will ensure uninterrupted learning in educational institutions in future. This study in addition recommends that it is important to ensure that the Ministry of Education, parents and teachers support vulnerable students to ensure they are not exploited and that no learning loss occurs even as schools delay re-full opening until January 2021 despite grades 4, class 8 and form 4s being back in schools already. Keywords: Covid-19, Pandemic, Education system, Students, teachers, Parents, Kenya.
Keywords: Covid-19; Education system; Kenya; Pandemic; Parents; Students; teachers; ⛔ No DOI found

Can Facebook groups enhance continuing professional development of teachers? Lessons from Kenya - Bett, Harry; Makewa, Lazarus (Asia-Pacific Journal of Teacher Education, 2020)
Continuing Professional Development (CPD) for teachers in Kenya suffers from challenges such as inadequate resources, poor planning, competing interests, among others. Besides being traditional in approach, most CPD sessions are far between to be meaningfully helpful. With increasing uptake of technology and number of social media users in Kenya, Facebook can be a potential platform to enhance teachers’ professional development. This exploratory cross-sectional survey focussed on discussions teachers had in the month of February 2015 on one Facebook Group named ‘Teachers of English’. A directed content analysis of the 647 posts following Shulman’s category of teacher knowledge base revealed that interactions on the group centred on the teaching of English and Literature, as well as on other education-related matters. This study concludes that that Facebook Groups can be fertile avenues for teachers’ ongoing professional development, especially in developing countries where such opportunities are scarce.
Keywords: Content analysis; Education--Teaching Methods And Curriculum; English teachers; Facebook Groups; Kenya; Professional development; Social networks; Teacher education; Teachers; __:import:02; __:match:final; __:matched; __:study_id:2425933; __finaldtb; professional development

Kenya: Heavy Rains and Flooding Update #7 (19 June 2024) - OCHA (2024)

Basic Education Infrastructure - Kenya Vision 2030 (2020)

Draft Value Added Tax (Digital Marketplace Supply) Regulations, 2020 - Kenya Revenue Authority (2020)

Radio Timetable 2020 - Kenya Institute of Curriculum Development (2020)

Edu TV Channel 2020 - Kenya Institute of Curriculum Development (2020)

Survey Report on Socio Economic Impact of COVID-19 on Households - Kenya National Bureau of Statistics (2020)

The Promise of Inclusive Digital Learning in Kenya - Government of Kenya (2022)

Kenya Digital Master Plan 2022-2032 - Republic of Kenya ICT Authority (2022)

Keep Kenya Learning (KKL): Training to Engage Caregivers in Digital Learning - Keep Kenya Learning (2022)

Kenya Basic Education COVID-19 Emergency Response Plan - Ministry of Education, Republic of Kenya (2020)

Kenya Basic Education COVID-19 Emergency Response Plan - Ministry of Education, Republic of Kenya (2020)

Report of the Presidential Working Party on Education Reform: ​​Transforming education, training and research for sustainable development in Kenya - Government of Kenya (2023)

Policy on Information and Communication Technology in Education and Training | Ministry of Education - Kenya - Republic of Kenya Ministry of Education (2021)

Adolescents (age 10 - 19) presenting with pregnancy at health facilities - Kenya Health Information System (KHIS) (African Institute for Development Policy, 2020)
Rates of adolescent pregnancy are once again on the rise in Kenya.  The sudden surge threatens to cut short the pursuit for education and opportunities for especially vulnerable girls in the country.

Promises to keep: impact of COVID-19 on adolescents in Kenya - Presidential Policy and Strategy Unit (Kenya); Population Council (2021)

Education Sector Budget Proposal Report 2023/24 - Government of Kenya (Government of Kenya, 2023)

Brief 1 - How DPL can support FLN and equitable learning in Kenya - Hinks, Jessica; Daltry, Rebecca (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Helping improve the Kenya Education Cloud with a SWOT analysis - Groeneveld, Caspar; Kimenyi, Eric; Kaye, Tom (EdTech Hub, 2021)
In early 2021, EdTech Hub partnered with the Kenya Institute of Curriculum Development to support them to analyse the strengths, weaknesses, opportunities and threats of the Kenya Education Cloud. This blog highlights what we learnt, and lessons that can inform the development of Virtual Learning Environments around the world.  Governments all over the world responded to Covid-19 school closures by…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Under the Hood of an EdTech Study in Kenya: Implementation challenges, successes, and lessons learnt - Büchel, Konstantin; Crossley, Colin; Cullen, Claire; Letsomo, Thato (EdTech Hub, 2023)
In the years following a global pandemic that left 1.6 billion learners out of school, the global learning crisis has grown more urgent. Governments worldwide have sought technology-enabled education platforms that can support higher quality, resilient education systems. One cheap and easy tool for delivering remote educational support is basic mobile phones, which represent a potentially cost-effective and remote platform for adapting a range of proven pedagogical methods. To do so successfully, programme delivery should consider three key factors that include (1) careful training on delivering pedagogical methods in a phone setting, (2) Appropriate monitoring systems to ensure weekly delivery fidelity and, (3) an appropriate data and/or delivery infrastructure to enable programme monitoring. If done successfully, mobile phone programmes can present education ministries with an efficient delivery option for quality education at a fraction of the cost of higher-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Equality of Usage of Personalised Learning Software: Key Findings from EdTech Hub and EIDU’s Sandbox in Kenya - Rahman, Asad; Tanveer, Rabia; Olwala, Tess; Musungu Ongadi, Allan; Freidberg, Aidan; Munialo, Indrah (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Algorithmic design in EdTech: Investigating adaptivity for learners and teachers in a digital personalised learning tool in Kenya - Moustafa, Nariman; Daltry, Rebecca; Major, Louis; Sun, Chen (EdTechHub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Raising readers: Kenya schools use of technology to improve parent and carers' engagement in literacy learning: Inception Report - Nicolai, Susan; Zubairi, Asma; Bapna, Akanksha; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Learners and Caregivers' Barriers and Attitudes to SMS-based Mobile Learning in Kenya: Key findings from a telephone survey - Jordan, Katy; Damani, Kalifa; Myers, Christina; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

SWOT Analysis of the Kenya Education Cloud - Groeneveld, Caspar; Kimenyi, Eric; Kaye, Tom (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _cover:v3; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Government-led edtech initiatives to improve learning outcomes in Kenya (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Kenya Institute of Curriculum Development (2020)

Kenya Institute of Special Education (2020)

Access to electricity (% of population) - Kenya - World Bank (2020)

Low-Tech Personalised Learning to Improve Girls' Education in Kenya - EdTech Hub (EdTech Hub, 2021)

Empowering self-help groups for caregivers of children with disabilities in Kilifi, Kenya: Impacts and their underlying mechanisms - Bunning, Karen; Gona, Joseph K.; Newton, Charles R.; Andrews, Frances; Blazey, Chantelle; Ruddock, Hannah; Henery, Jessica; Hartley, Sally (PLOS ONE, 2020)
Bringing up a child with disabilities in a low-income setting is challenged by inadequate resources, limited psycho-social support and poverty. Not surprisingly, many caregivers experience fatigue, distress and isolation. To address and investigate these issues, action was taken to set up twenty self-help groups focusing on caregiver empowerment. A realist evaluation design was adopted to evaluate impacts associated with the self-help process and to identify mechanisms determining the outcomes. Monthly monitoring visits were conducted to the groups during a ten-month set-up period, at the end of which eleven active groups remained, nine having dissolved due to disputes, corruption and extreme environmental conditions. A facilitated intervention was delivered to the active groups (N = 154) over a six-month period. The members were guided to review and discuss topics such as economic empowerment, personal situation, peer support, community inclusion, access to health and education. Evaluation employed mixed methods using questionnaires (n = 75) and semi-structured interviews (n = 36) pre- and post-intervention. At baseline, the burden of caregiving was characterised by aloneness, challenges, stigma and discrimination. Post-intervention, caregiver agency was defined by togetherness, capacity-building, acceptance and well-being. Significant impacts associated with caregiver perceptions included increased social support, reduced severity of child’s disability and decreased effects of extrinsic factors affecting the caregiver’s role. Mechanisms of ‘handling goods and money’ and ‘social ties and support’ appeared to underpin the outcomes. Caregiver empowerment was associated with newly developed skills, social connectedness and resource mobilisation. Documentation of group processes contributes to the evidence on community-based inclusive development.
Keywords: Caregivers; Child abuse; Children; Disabilities; Finance; Food; Human families; Social discrimination

Out of 47.6 million Kenyans, 35.7 million are under the age of 35 - Ndungu, Tonny (Citizen Digital, 2020)
Kenya is a country of the youth according to the 2019 Census results which shows that 75% of the  47.6 million population is under the age of 35.

How school closures during COVID-19 further marginalize vulnerable children in Kenya - Jepkemei, Damaris Seleina Parsitau and Evelyn (Brookings, 2020)
School closures in Kenya have devastating consequences for marginalized learners.

Improving Early Grade Education Across Kenya - RTI International (RTI, 2022)
Tusome focuses on four key interventions developed and proven to improve literacy outcomes in Kenya. Learn about the impact of this program.

Drought situation in the Kenya ASAL areas now at crisis level - Kenya | ReliefWeb - ASAL Humanitarian Network (2022)
News and Press Release in English on Kenya about Agriculture, Climate Change and Environment, Drought and more; published on 5 Oct 2022 by ASAL Humanitarian Network

Mobile Penetration and Growth in Kenya - Kibuacha, Frankline (GeoPoll, 2021)
Kenya is one of the most technology-advanced countries in Africa, which has had many christen it the Silicon Savannah, powered by its mobile penetration.

Engaging parents and caregivers in EdTech is critical to foundational learning in Kenya - Nicolai, Susan; Khan, Amina; Mwachi, Joan; Otieno, Jennifer Cotter (EdTech Hub, 2022)
Kenya, sometimes called the ‘Silicon Savannah’ of Africa, is home to one of the most vibrant EdTech ecosystems in Africa (see Otieno & Taddesse, 2020). Building on government initiatives such as the flagship Digital Literacy Programme (DLP), the country’s Covid-19 education response (Ngware & Ochieng, 2020) included tremendous efforts to provide distance learning solutions. This week, the Kenya EdTech Summit 2022 is bringing together many of those who have been making this happen to discuss the role of evidence and collaboration to accelerate the pace of progress in Kenya.

Virtual learning under lockdown casts doubt on Kenya as the Silicon Savannah - Miller, Noah (Africa at LSE, 2020)
Kenya's response to the COVID-19 epidemic challenges its reputation as the Silicon Savannah when it comes to the switch to digital education.

Collaboration to Realise Kenya’s National Learning Goals through EdTech - Otieno, Jennifer; Omuthe, Ronald; Ampofo, Rudolph (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

M-Lugha: Improving Student’s Access to Literacy and Numeracy by using Local Language Instruction in Northern Kenya - Cordeiro, Paula (Global Ed Leadership, 2021)
Abdinoor Alimahdi is a former telecommunications engineer from Kenya. He is an Award winning EdTech innovator and social entrepreneur. Some of the awards include:  Best 100 startups (StartupIs…

Needed: An Ecosystem for Meaningful Digital Innovation in Northern Kenya - Aslan Afrika (Aslan Afrika, 2021)
The information and communications technology (ICT) industry thrives in Kenyan cities, but vast rural tracts in Northern Kenya are stranded on the wrong side of the digital divide. One of the weakest links is a lack of infrastructure, both for […]

Putting girls’ education first in Kenya | Blog | Global Partnership for Education - GPE (2020)
With support from the Global Partnership for Education, the Government of Kenya is making strides in ensuring that all girls – including those living in the poorest and most remote areas of the country - have access to quality education.

Climate Change and Education in Kenya - Fitzpatrick, Rachael; Amenya, Donvan (Education Development Trust, 2023)
What impact does climate change have on education, especially in areas which are vulnerable to climate disasters and extreme weather events? In this report, we explore the impact of climate change on schools and learning in six counties in Kenya (Nairobi, Mombasa, Turkana, Tana River, Kwale and Kilifi).

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Testing Digital Timer Tools to Support Early Grade Lesson Delivery - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the second in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates whether introducing a timer alongside digitised lesson plans impacts upon teachers’ lesson plan usage. The A/B test found that providing a timer did not influence how much time teachers spent on digitised lesson plans. While, on average, teachers in the timer group tended to spend less time on lesson plans for literacy and more for numeracy, this was not statistically significant. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; timer; lesson plan An output of EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

The impact of online learning as emerging technology on parents: Case study of parents of primary school children in Nairobi, Kenya. - Emmanuel, Jadesola; Oduor, Collins (Journal of Language, Technology & Entrepreneurship in Africa, 2021)
Kenya, as a nation has a stable schooling system based on synchronous classroom learning. The advent of the COVID 19 pandemic has led to the sudden shift in paradigm to remote schooling learning systems. Several studies have been carried out on remote schooling systems and the impact of parent’s involvement in children’s remote school, but none has been sighted on its impact on parents. The objective of this study was to determine the impact of the sudden paradigm shift on parents of remote schooling pupils in Kenya during this pandemic. A descriptive survey design was utilized. Primary data was collected by online questionnaires and secondary data from past studied. The analysis was done with a statistical application. It was found out that, remote schooling may be easily accepted by many Kenyan parents with 39.8% of parents indicating that they will recommend remote schooling having indicated some benefits derived from it and 24.8% indicating that they will not. It was therefore recommended that the national government should address factors that may hinder effective remote learning, thus encouraging parental involvement and support. It was also recommended that the government and education practitioners should officially develop and implement standards and curriculum for the implementation of remote learning in Kenya in preparation for future pandemics. Keywords: remote schooling, remote learning, descriptive survey design
Keywords: ⛔ No DOI found

Kenya: Registered refugees and asylum-seekers as of 31 March 2025 - UNHCR (UNHCR Kenya, 2025)

Professional Development on Digital Literacy and Transformative Teaching in a Low‐Income Country: A Case Study of Rural Kenya - Kerkhoff, Shea N.; Makubuya, Timothy (Reading research quarterly, 2022)
In recent years, the government of Kenya has implemented programs with the hope of moving the country to middle‐income status. The government has implemented the Digital Literacy Programme, distributing tablets to schools across the country, and also a new curriculum, promoting innovative teaching that includes digital literacy, learner‐centered teaching, and relevance to students’ lives. Our purpose in this research was to explore culturally sustaining teaching methods in line with the Kenyan government’s push for innovative teaching and digital literacy attainment for all students. We used case study methods to describe Kenyan teachers’ perceptions of innovative teaching and digital literacy while participating in the Inquiry Initiative, a three‐day professional development series. Participants included preschool, primary, and secondary teachers from Trans Nzoia County. Data sources were pre‐ and post‐surveys, participant‐generated artifacts, and interviews. Our participants perceived the following needs: new literacies for learners, creativity for learners, collaboration and group work, and creativity to overcome technological challenges. Overall, participants embraced learner‐centered teaching theoretically but found that the lack of technological resources created barriers to teaching digital literacy in a learner‐centered fashion. We found that teachers reported mostly using technology for teaching preparation and record keeping rather than engaging students in digital literacy practices. To solve technological challenges, teachers described having students work in groups and using smartphones. Future research could share more creative solutions to technical challenges in low‐income countries.
Keywords: 1‐Early childhood; 2‐Childhood; 3‐Early adolescence; 4‐Adolescence; 6‐Adult; Case Studies; Collaboration; Collaborative Learning; Computer literacy; Constructivism; Creative ability; Creativity; Critical Pedagogy; Culturally Responsive Pedagogy; Digital Literacies; Digital literacy; Digital/media literacy; Education & Educational Research; Educational technology; Gloablization and Literacy; Group work in education; Information literacy; Instructional strategies; methods and materials; Kenya; Literacies; Literacy; Literacy programs; Policy; Postcolonialism; Professional Development; Psychology; Psychology, Educational; Qualitative Research; Social Constructivism; Social Sciences; Socio‐cultural; Students; Study and teaching; Survey Research; Teacher attitudes; Teacher education; Teacher education; professional development; Teachers; Teaching; Teaching methods; Team learning approach in education; Transformative

What is 'Nudging' and How Does it Change Behaviour in Education? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the behaviour change strategy of leveraging concise messages at strategic decision points (i.e., ‘nudging’) to influence the behaviour of a recipient towards a desired outcome. We focus on EdTech Hub’s work concerning nudge messaging. It builds on work from messaging interventions in Ghana and Kenya, linking these to the broader literature on the topic. It emphasises that although there is a strong and growing evidence base for nudge technologies, effective implementation remains dependent upon context-specific adaptation. It is not inevitable that nudge messaging interventions will lead to positive outcomes — indeed, outcomes are often mixed. It is therefore vital to understand the specific impacts of interventions on particular groups of recipients. We present findings and recommendations that should inform how nudging technologies in education are approached and what decision-makers need to consider in order to ensure uptake and minimise risks. Lastly, we explore areas that require further research, namely, the changing nature of nudging due to artificial intelligence, the safeguarding risks of nudging, persisting questions about cost-effectiveness, and how nudging can more specifically target learning. Keywords: Behavioural psychology; EdTech; education; messaging; nudging; participation An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Designing Digital Notifications to Support Teacher Uptake of Data Dashboards - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the fourth in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the extent to which the provision of notifications to pre-primary teachers to view data dashboards impacts learner device usage and learning outcomes. The A/B/C test found no impact on device usage and negligible impact on learning outcomes. This suggests that accompanying data dashboards with notifications did not influence pedagogical practice in a way which impacted on learning. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; notification system An output of EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Disaster Management Preparedness in the Education Sector in Kenya – A Case of the COVID-19 Pandemic. - Ngari, Prof Fr Stephen Mbugua; Ndung’u, Stephen W. (Editon Consortium Journal of Educational Management and Leadership, 2020)
This study examined the disaster management preparedness in the education sector in Kenya, with a focus on the COVID-19 pandemic period. The study adopted destktop literature review for data collection. The collected data pertains e-learning in Kenya and in other countries during the time of  the novel coronavirus pandemic. Notably, the education sector, like in many other countries, seeks to actualise the Millennium Development Goals (MDGs) in line with the United Nations and the Education for All (EFA) movement lead by UNESCO (MacEwen, et al., 2011). Examples of these events are; accidents such as the one evident in Kakamega Primary School where the school closed for about two weeks (Daily Nation, 2020), attack by militia groups as was the case of Garissa University in 2015, intercommunity wars that lead to displacements, famine, and fires. These disasters and events, whenever they strike, have led to the closure of affected institutions of learning to pave the way for interventions. Garissa University is a leading example since it had to close for about nine months in 2015-2016 (BBC, 2016). In Kenya, disasters and other events disrupt the progress towards achieving MDGs and EFA time to time, and that was the inspiration for this study. The study concludes that disasters like nature patterns, militia groups, electricity faults, and those instigated by learners can derail learning in education and cause loss of lives. As such, online learning comes in handy to lessen such disasters. The possibility of such learning model has been tested and proved during COVID-19 pandemic and it has been successful in many institutions of higher learning and middle level colleges.
Keywords: COVID-19 Pandemic; Disaster Management; Education Sector; Preparedness

Investigating the Impact of Content Repetition on Digital Personalised Learning Tools for Early Grade Learners - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the third in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the impact of repeating learning content for pre-primary learners on learner device usage and learning outcomes. The A/B test found that content repetition had an impact on literacy and numeracy outcomes for PP2 learners. PP2 learners’ usage of the DPL tool was significantly reduced with content repetition. However, considering the small size of the mixed-methods sample, caution should be taken when interpreting these results. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; repetition An output of EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Optimising Session Duration on Digital Personalised Learning Tools for Early Grade Learners - Sun, Chen; Moustafa, Nariman; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the first in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the optimal number of minutes for pre-primary learners on a classroom-integrated digital personalised learning tool to optimise learning outcomes. The A/B/C test found different levels of session duration impacted on literacy and numeracy outcomes, with the findings for numeracy dependent on grade level. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; session duration An output of EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Adoption of education technologies for learning during COVID-19 pandemic: The experiences of marginalized and vulnerable learner populations in Kenya - Ochieng, Vollan Okoth; Waithanji Ngware, Moses (International Journal of Educational Reform, 2022)
The onset of COVID-19 made governments and other education actors prioritize distance learning, particularly through education technologies (EdTechs). Most sub-Saharan African countries adopted and adapted this approach. This paper examines the extent of EdTechs’ deployment in Kenya during the COVID-19 pandemic among marginalized and vulnerable populations. A cross-sectional study design was adopted for the study from which this paper drew its data, with both secondary and primary data utilized. The findings show that marginalized/vulnerable learner populations are still left out on EdTech supported learning. This article proposes salient recommendations that could help advance inclusive education discussion and related EdTechs’ discourse.

Low-connectivity Educational Technology: A Case Study of Supporting Learning during Covid-19 via SMS with ‘Keep Kenya Learning’ - Jordan, Katy; Mumbi, Albina; Khagame, Phoebe; Njuguna, Lydia (Journal of Learning for Development, 2024)
The use of Short Messaging Service (SMS) for education has grown in recent years, drawing particular attention to supporting school-level learners, due to the Covid-19 pandemic. This renewed interest has prompted questions about how this form of educational technology could be used in the longer term. However, despite being used in many Covid-19 responses, there are few documented examples of innovative applications in this field during the pandemic, which represents a gap in the literature. As a medium for education, SMS offers potential benefits such as being cost-effective and having positive impacts on learning. In this paper, we present a case study of an educational programme rapidly implemented during the pandemic as part of the ‘Keep Kenya Learning’ program, to support learners remotely in terms of literacy, numeracy, and social and emotional learning topics. Through the case study, we describe the innovative process used to rapidly develop content for SMS, and draw upon usage statistics, quiz scores and user feedback to gain insights into its implementation with learners and caregivers in Kenya. The case study demonstrated that educational television content can be effectively adapted to mobile delivery. Furthermore, we present practical reflections on the development and implementation of SMS educational technology which will help inform future initiatives. These include considering timing in relation to school terms when planning a supporting intervention, and designing content in a modular way to allow flexibility for learners in navigating through courses.

Stakeholders’ perspectives of enablers and barriers to successfully implementing an integrated early childhood development program in an informal urban settlement in Kenya - Ssewanyana, Derrick; Martin, Marie-Claude; Angwenyi, Vibian; Kabue, Margaret; Proulx, Kerrie; Zhang, Linlin; Malti, Tina; Njoroge, Eunice; Nasambu, Carophine; Marangu, Joyce; Odhiambo, Rachel; Ombech, Eunice; et al. (SAGE Open, 2023)
Integrated early childhood development (ECD) programs boost child health and developmental outcomes. However, the factors contributing to the successful implementation of such programs in informal urban settlements are not well researched. We conducted 14 focus group discussions and 13 key informant interviews with 125 caregivers of children under the age of 5 years and stakeholders, exploring their views on enablers and barriers to implementing an integrated ECD program in an informal settlement in Kenya. Strategic engagement, capacity building, transparency, fair compensation of ECD workforce, communication skills, and the need to tailor ECD programs to local realities were discussed. An equity-focused implementation approach for integrated ECD programs is timely.

Supporting equitable access to learning via SMS in Kenya: Impact on engagement and learning outcomes - Jordan, Katy; Myers, Christina; Damani, Kalifa; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia (British Journal of Educational Technology, 2024)
Abstract The use of SMS messaging for education has grown in recent years, with particular attention recently during the Covid‐19 pandemic. Mobile phones often have high levels of ownership in low‐income contexts compared to computers, and lower connectivity requirements, which arguably make this a more equitable medium than data‐heavy online instruction, for example. However, given that gender can be a factor to influence mobile device access and use, it is also important to consider educational applications through a gender lens, to avoid further exacerbating digital divides. In this paper, we present an analysis of server log and evaluation data in relation to a literacy‐focused initiative for primary‐aged learners carried out in Kenya as part of the Tusome programme and through the SMS‐based M‐Shule education platform, which does not require an Internet connection or smartphone to run. The extent of engagement with the platform varies according to gender and location within the country. The data also demonstrate a positive impact on learning outcomes regardless of learners' gender and location. Furthermore, the learning gains are shown to be relatively cost‐effective in comparison with educational technology interventions in similar contexts. The findings show that this low‐connectivity adaptive model has a positive impact on learning outcomes. It is a scalable approach to support a range of learners in Kenya, providing more support to learners who need it, and leading to increased foundational learning outcomes overall. As such, the findings will also be of highly relevant to other low‐connectivity contexts. Practitioner notes What is already known about this topic Mobile phones can be used as a means to support learning, through mobile learning and SMS, particularly in low‐connectivity contexts, although there is a lack of rigorous evidence of impact upon learning outcomes. Mobile phone device ownership tends to be higher than computer or wired Internet connections in many low‐income contexts. Software applications which adapt to the learners' level have shown good potential for gender‐equitable learning outcomes in low‐income contexts; however, these often require an Internet connection in addition to computers or tablets to be run on. What this paper adds There is a lack of contextually relevant evidence of the impact of SMS‐based mobile learning applications in low‐resource and low‐connectivity contexts upon learning outcomes. Through analysis of data generated via an experimental design, this study provides evidence that literacy materials delivered through an SMS‐based educational platform—M‐Shule—can have a positive impact upon learning outcomes. Furthermore, gains are equitable in terms of learners' gender, and location, within Kenya. Implications for practice and/or policy Mobile phones can be an effective way of reaching learners to provide additional educational support as part of existing education programmes in low‐connectivity environments. Learning gains using M‐Shule are evidenced as significant and relatively cost‐effective. Existing high‐quality learning materials developed in other media can be effectively adapted to SMS to reach learners particularly who are out‐of‐school or during periods of educational disruption.

Learners and caregivers barriers and attitudes to SMS-based mobile learning in Kenya - Jordan, Katy; Damani, Kalifa; Myers, Christina; Mumbi, Albina; Khagame, Phoebe; Njuguna, Lydia (African Educational Research Journal, 2023)
The use of mobile phones has been identified as a potential way to bring the benefits of educational technology to a wider audience, including in low-connectivity settings. This is a topic that has received renewed interest recently as a result of the COVID-19 pandemic and school closures. While a number of recent studies have demonstrated good potential for mobile phones and SMS to be used to support learning, there are also questions about how equitable this medium is in practice. We conducted a telephone survey with learners (n = 122) and their caregivers (n = 124) who use M-Shule, an SMS-based educational platform in Kenya, in order to understand their attitudes towards mobile learning, and the benefits and constraints. In particular, we consider whether there are differences in responses according to gender and/or location, to shed light on whether use is equitable. We find that girls and boys face similar barriers to use, and the technology is perceived to be equally beneficial. We identify some areas for potential further support for all learners through mobile learning.

Distance learning during COVID-19 crisis: Primary and secondary school parents experiences in Kenya - Mabeya, Mary Theodorah (East African Journal of Education Studies, 2020)
The COVID-19 disease outbreak in 2020 was declared by the World Health Organization as a Public Health Emergency (PHEIC). Human symptoms of the Coronaviruses among others are commonly spread through droplets (coughing) and close personal unprotected contact with an infected person through toughing. Based on the speed at which the disease spreads, learning institutions were distinguished as high-risk areas with prospective of exposing both learners and instructors the spreading the virus. This had a serious effect on the academic programs in all learning institutions worldwide where learning was abruptly discontinued and all students and instructors send home. The Government of Kenya (GOK) through the President’s directives suspended all learning institutions as one of the measures taken by the Ministry of Health to mitigate the spread of COVID-19. This affected the learning since most of the schools had not even started their syllabus that academic year. Alternative measures to ensure that curriculum implementation progressed well; various mechanisms were suggested including remote learning which was actualised in some instances. Virtual lessons and Open and Distance e-learning (ODeL) has mainly been adopted by institutions of higher learning (colleges and universities) globally in offering online classes. However, this was not the case in many public primary and secondary institutions where the common form of learning involves a very interactive physical relationship between teachers and their learners in classrooms. In Kenya, since all institutions of learning were closed as a result of the breakout of the COVID-19 pandemic, the Ministry of Education (MOE) opted for remote learning across the country. Research results from Rangwe Sub-county have shown that most learners have not benefited much from the online classes due to the network and other related challenges reported in this paper. This has created education inequity since parents who have children in private schools and those from well of backgrounds are the ones enjoying distance learning programmes offered. The research has also found out that parents did no proper supervision to ensure that their children were committed in their studies in remote settings. Lack of supportive infrastructure (electricity and internet network access) limited children participation in distance learning programmes in Rangwe Sub-county. The paper recommends that government to properly educate parents, teachers and learners on modalities of distance and remote learning programmes. There is need for government to provide children from disadvantaged families with technological appliances to enable them to participate in distance education.

A Cautionary Tale of Tutoring Hard-to-Reach Students in Kenya - Schueler, Beth E.; Rodriguez-Segura, Daniel (EdWorkingPaper, 2021)
Covid-19-induced school closures generated great interest in tutoring as a strategy to make up for lost learning time. Tutoring is backed by a rigorous body of research, but it is unclear whether it can be delivered effectively remotely. We study the effect of teacher-student phone call interventions in Kenya when schools were closed. Schools (n=105) were randomly assigned for their 3rd, 5th and 6th graders (n=8,319) to receive one of two versions of a 7-week weekly mathfocused intervention—5-minute accountability checks or 15-minute mini-tutoring sessions—or to the control group. Although calls increased student perceptions that teachers cared, accountability checks had no effect on math performance up to four months after the intervention and tutoring decreased math achievement among students who returned to their schools after reopening. This was, in part, because the relatively low-achieving students most likely to benefit from calls were least likely to return and take in-person assessments. Tutoring substituted away from more productive uses of time, at least among returning students. Neither intervention affected enrollment. Tutoring remains a valuable tool but to avoid unintended consequences, careful attention should be paid to aligning tutoring interventions with best practices and targeting interventions to those who will benefit most.

The potential and prerequisites of effective tablet integration in rural Kenya - Heinrich, Carolyn J.; Darling-Aduana, Jennifer; Martin, Caroline (British Journal of Educational Technology, 2020)
This study investigates how pedagogical, cultural and institutional factors interact with technical knowledge in educational technology integration and how they relate to equitable and effective technology use in low-resource settings. In the context of a one-to-one tablet initiative in rural Kenya, we explore how these factors constrain or support access to technology, instructor capacity, student engagement and student learning, as well as their implications for reducing educational and digital divides. We employ a mixed methods, such as a quasi-experimental (prepost, nonequivalent control group) research design that draws on data from classroom observations, teacher interviews, student surveys and focus groups, and assessments of student academic performance to generate evidence on classroom practices and student learning in schools with access to tablets, while also highlighting core challenges to successful technology integration. Our findings contribute to the identification of prerequisites and supporting factors for successful educational technology integration, as well as policy levers and school-based strategies that are likely to increase equitable access to quality learning experiences in schools in low-resource contexts. Practitioner Notes What is already known about this topic A lack of funding, planning and infrastructure hinder information and communication technology (ICT) integration. Procurement of educational technology and infrastructure improvement efforts has reduced digital divides, but learning divides persist in implementation. Insufficient teacher technology expertise and professional development constrain teacher's effective use of educational technology in classrooms. What this paper adds We employ mixed methods—triangulating the student assessment data with data from student surveys and focus groups, teacher interviews and classroom observations—to identify how pedagogical, cultural and institutional factors interact with technical knowledge in ICT integration in ways that support or constrain student learning in low-resource contexts. We find that more attention is needed for cultural factors that interact with pedagogical and technical skills to ensure that the classroom instructors' attention is equitability distributed in ways that discourage in-class “tracking” and differential access to quality learning experiences, such as some teachers' disregard of “slow learners” in the classroom. In low-resource contexts, providing even basic levels of infrastructure (eg, a consistent power source) and access to general technical knowledge requires more creative and concerted efforts from school leadership and instructors, such as the offer of tutorials and reading clubs outside of the class to expand access and improve the use of devices. Implications for practice and/or policy We find that device sharing can have positive effects on peer-to-peer learning, which suggests that policymakers in Kenya should weigh the benefits of achieving one-to-one device access against the potential advantages of alternative investments, such as expanding professional development on the integration and use of currently available devices. Increasing opportunities for peer-to-peer learning and exchange (among teachers and students) and building shared capacities for ICT integration can help reduce technical issues and lost instructional time.

Leadership Roles in Managing Education in Crises: The Case of Kenya During Covid-19 Pandemic - Mbogo, Rosemary Wahu (2020)
Covid-19, a disease caused by a novel coronavirus (SARS-CoV-2) was first reported in Wuhan, China, in December 2019 and in Kenya in March 2020. In Kenya, the Covid-19 pandemic has brought to light some unknown talents among the stakeholders at different levels. The economic sector has had manufacturing potential for goods, and from mass media reports, this has been demonstrated through production of Personal Protective Equipment (PPEs), ventilators and innovations in technology in the creation of apps such as the Linda App for contact tracing and Gumzo, a video conferencing app. Similarly, the education sector has also demonstrated potential for adaptation in some situations. For example, after all institutions of learning were closed to prevent the spread of coronavirus in March 2020, many universities have continued learning through Online, Distance and E-learning (ODEL) platforms, and some have even conducted virtual graduations. Others like Kenyatta University have reported innovations such as development of ventilators and modified testing swabs for Covid-19. This is admirable despite numerous limitations of internet accessibilities and other shortcomings. This remarkable achievement has been possible due to semi-autonomy in the university education sector, where Senates are given the right and power, by the Education Act, to make autonomous decisions for their universities which are regulated and monitored using the standards and regulations set by the Commission of University Education (CUE). However, other levels of the education sector do not have this autonomy and have had to depend on the ministry of education for guidance. On 8th July 2020, the ministry of education announced the result of a consultative meeting with stakeholders, to postpone the reopening of schools to January 2021. This was due to the rising cases of corona virus infections in May and June, steeping the infection curve, expected to reach the peak by November and to have flattened by January 2021 (Magoha, 2020). However, what surprised many was the additional and unforeseen announcement that all basic education students (apart from standard 8 and form 4 examination candidates whose details were not clarified) will repeat their current class levels in 2021. The pronouncement caused anxiety and has attracted mixed reactions from various stakeholders. The purpose of this paper is therefore to explain the leadership decisions made by the ministry of education analyze their impact on basic education and propose possible ways for educational leaders and administrators, community leaders and volunteers to facilitate home-based education during the Covid-19 pandemic. This should be done with a goal for progression and promotion of students to the next class level when the 2020 syllabus is eventually covered. The study method utilized desktop literature research where interactions with educational leaders, scholars and practitioners were used to investigate threats and opportunities in managing education during crises.  Article visualizations

Parent and implementer attitudes on gender-equal caregiving in theory and practice: Perspectives on the impact of a community-led parenting empowerment program in rural Kenya and Zambia - Okelo, Kenneth; Onyango, Silas; Murdock, Dawn; Cordingley, Kaylie; Munsongo, Kelvin; Nyamor, George; Kitsao-Wekulo, Patricia (BMC Psychology, 2022)
Fathers are often perceived to be mainly responsible for the provision of the family's economic needs. However, past studies have demonstrated that fathers’ involvement in parenting has great significance for the child’s holistic growth and development. Few studies have investigated fathers’ roles in the nurturing care of young children, particularly responsive care and stimulation, in sub-Saharan Africa. The study reported here was carried out as part of a larger study that sought to evaluate the effectiveness of the Moments That Matter (MTM) program in improving the nurturing care of young children in rural communities in Zambia and Kenya. The MTM program uses a parenting empowerment approach to promote bonding and interactions between caregivers and their children within the home, focusing on responsive care, early learning, and security and safety so that children reach their full developmental potential. Trained volunteers facilitated monthly primary caregiver support and learning groups and ECD home visits. Fathers were encouraged to participate in the home visits and to attend some of the group meetings on specific topics. The study reported in this paper aimed to establish the impact of the parenting empowerment program in promoting more gender-equal attitudes and practices on parenting among fathers (who were not the primary caregivers).
Keywords: And holistic development; Childcare; Early childhood development; Early learning; Fathers’ perceptions; Fathers’ practices; Fathers’ roles; Parenting; Responsive care; Stimulation

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Fathers’ engagement in a parenting program primarily intended for female caregivers: An early qualitative process evaluation in Western Kenya - Jeong, Joshua; McCann, Juliet K.; Bhojani, Alina; Maguet, Zane; Uyehara, Malia; Ochieng, Michael (PLOS Global Public Health, 2024)
Parenting programs predominantly target one caregiver of the child or most commonly the child’s mother. However, fathers are also important caregivers whose engagement in interventions can benefit child health, nutrition, and development. In August 2023, a qualitative process evaluation was conducted during the first quarter of implementation to assess initial fidelity, quality, and outcomes of a parenting program in rural Western Kenya. In-depth interviews were conducted with female and male caregivers along with in-depth interviews and focus group discussions with program delivery agents. This secondary analysis specifically focused on stakeholders’ perceptions of father involvement in the program and aimed to identify barriers and facilitators to fathers’ participation, initial program impacts when fathers were involved, and recommendations for increasing father inclusion. Thematic content analysis was conducted, and data were triangulated across stakeholder groups. Overall, relatively few fathers participated in the program. Nevertheless, for the rare cases of participating fathers, stakeholders highlighted positive changes in fathers’ caregiving attitudes and practices. Key barriers to fathers’ program engagement included restrictive gender norms and perceived opportunity costs. Stakeholders suggested several strategies for better reaching fathers, including providing financial incentives and flexible scheduling of sessions. Overall, we found that fathers’ participation and program experiences were starkly different from those of mothers. Gender-responsive program adaptations and father-targeted implementation strategies are likely to increase the fathers’ engagement in parenting programs, which in turn may facilitate greater program impacts on family caregiving and child outcomes. Future evaluations of parenting programs should combine qualitative and quantitative approaches to more comprehensively assess program impacts on fathers and over time.

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Are Our Children Learning? The Status of Remote-learning among School-going Children in Kenya during the Covid-19 Crisis - Usawa Agenda (Usawa Agenda, 2020)

Teachers Learning Together: Large-scale approaches to teacher communities of practice - Rossignoli, Serena; Amenya, Donvan; Kamana, Dieudonne; Tiganescu, Andrea; Kudenko, Irina (Education Development Trust, 2020)
Keywords: C:Kenya / Rwanda

Report of the Standing Committee on Finance and Budget on the Third Basis for allocating among the counties the share of national revenue - Parliament of Kenya (2020)

ICT in Education and Training Policy - Republic of Kenya. (2021)

Kenya basic education COVID-19 emergency response plan - State Department of Early Learning and Basic Education (Republic of Kenya Ministry of Education, 2020)

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

Public Statement on the Status of Payments to County Governments FY 2021-2022 - Republic of Kenya National Treasury and Planning (2022)

Ministry of East African Community (EAC), ASALs And Regional Development - The Ministry of East African Community, Arid and Semi-Arid Lands, Republic of Kenya (2022)

Literacy rate, adult total (% of people ages 15 and above) - World Bank (2020)

The National Treasury and Planning (@KeTreasury) - The National Treasury and Planning (Twitter, 2020)

Teachers Service Commission (2020)

Centre for Mathematics, Science and Technology Education in Africa (2020)

Loon (Loon, 2020)
Loon is a network of stratospheric balloons designed to bring Internet connectivity to rural and remote communities worldwide.

Microsoft (2020)
Microsoft, en tant qu’acteur de la transformation numérique en France, aide les individus et les entreprises du monde entier à exploiter pleinement leur potentiel.

Kytabu – African Schools Online - Kytabu Company Ltd (2020)

EdTech, Learning and Equity: The EdTech Hub Research Portfolio - Haßler, Björn; Wagner, Dan; Outhwaite, Laura (EdTechHub, 2023)
Keywords: _internal; _r:AddedByMyEducationEvidence

A rapid scan of the EdTech landscape in 11 countries - Taddese, Abeba (EdTech Hub, 2020)
By Abeba Taddese We have just produced rapid scans of the EdTech landscape in 11 countries: Ghana, Jordan, Kenya, Liberia, Nigeria, Pakistan, Rwanda, Senegal, Sierra Leone, Tanzania, and Zimbabwe. The scans are based primarily on desk research and offer a glimpse into the countries’ EdTech ecosystems. They examine enabling factors for EdTech from a holistic systems perspective but are by…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Using innovative methods to train teachers of blind children: what we learned - Kweyu, Ignatius; Koszorus, Ferenc (EdTech Hub, 2021)
Governments all over the world have closed learning institutions because of the Covid-19 pandemic, including in Kenya. This has exacerbated the global learning crisis and made it more difficult for teachers, parents, and caregivers to include children with disabilities in quality education. To ensure learners with disabilities were not left behind during Covid-19 school closures, eKitabu partnered with EdTech Hub…
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Digital Personalised Learning to Improve Numeracy Outcomes in Kenyan Primary School Classrooms - EdTech Hub (EdTech Hub, 2021)

Let's Read — How Tusome Leveraged EdTech to Improve National Learning Outcomes. Governing Digital Transformation: Improving Outcomes in Education Systems - Myers, Christina; Kaye, Tom; Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 2: Insights from user research - Rahman, Asad; Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the second of five reports on the development of a proof of concept for the Hub. It provides a summary of user research undertaken for the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest. Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 1: Inception Report - Groeneveld, Caspar; Michels, Guillaume; Kaye, Tom (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the first of five reports on the development of a proof of concept for the Hub. It provides a background and overview of the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Designing for Scale: Understanding design principles and learning process for a personalised learning platform in Kenya - EdTech Hub (EdTech Hub, 2022)

Guidance Note on Education Data Mapping in Sub-Saharan Africa: Moving from theory to practice - Selwaness, Irene; Adam, Taskeen; Lawson, Laté; Heady, Lucy (EdTech Hub, 2022)
Keywords: _r:AddedByZotZen

An exploratory investigation into the factors related to EdTech use among Kenyan girls - Watson, Joe; Baier, Jasmin; Mughogho, Winnie; Millrine, Mark (British Journal of Educational Technology, 2023)
This paper contributes to the scarce literature on factors affecting EdTech use in households. These factors were considered through exploratory mixed-methods analyses of cross-sectional data on Kenyan girls and caregivers, captured during the COVID-19 pandemic. Quantitative analysis of the child dataset (n = 544) suggested the importance of both structural factors—such as technology hardware availability—and non-structural factors—including caregiver permission. Findings were supported by a thematic analysis of interview data from girls' caregivers (n = 58), which emphasised the role they play in girls' use of EdTech. Interviews also highlighted numerous caregiver concerns with EdTech, related to the relevance and rigour of educational content, the possibility of children accessing age-inappropriate material and child health (especially eyesight). Policy makers could alleviate these concerns by providing guidance on EdTech use and clearly signalling their approval of verified initiatives. Practitioner notes What is already known about this topic EdTech can benefit girls' education, yet there are various barriers to it being used. Existing research shows clearly that EdTech use can be impeded by structural factors (eg, hardware ownership). However, we find insufficient empirical evidence on the role of non-structural or behavioural factors. What this paper adds This paper addresses this gap, using a mixed-methods approach to explore the influence of 33 different measures (including non-structural factors) that could affect the number of hours girls spend using EdTech at home. Findings from a quantitative sample of girls (n = 544) and a qualitative sample of girls' caregivers (n = 58) highlighted the importance of non-structural factors, especially caregiver permission. The variable most strongly associated with girls' EdTech usage in our selected quantitative model concerned whether this was sanctioned by their caregivers. Our qualitative data suggested why caregiver permission to use EdTech might be withheld: caregivers emphasised perceived concerns about the risks and rigour of EdTech. Implications for practice and/or policy Our findings suggest the viability of policy interventions that provide EdTech guidance to caregivers. Caregivers uncertain about EdTech could be reassured of the appropriateness of verified initiatives, while those already convinced might be aided in their attempts to support EdTech learning. Such guidance could provide a low-cost means of further exploiting the benefits that household EdTech learning can provide.
Keywords: COVID-19; EdTech; Kenya; caregivers; girls' education; ⛔ No INSPIRE recid found

Keep Kenya Learning Project (2021)

Population, total - Kenya | Data - World Bank (2021)

Worldreader (2020)
With low-cost technology, culturally-relevant digital books, and a network of partners, we’re helping millions of people read more and read better.

Population growth (annual %) - Kenya | Data - World Bank (2021)

Kenya's pioneering eLearning programme - iMlango (iMlango, 2022)
iMlango aims to improve education outcomes in maths, literacy & life skills for 180,000 children in 245 schools by delivering access to digital education services & content.

School enrollment, primary (% net) - Kenya | Data - World Bank (2021)

Lessons from Kenya’s Education Reforms - World Bank (2022)

Can Education be Standardized? Evidence from Kenya - Gray-Lobe, Guthrie; Keats, Anthony; Kremer, Michael; Mbiti, Isaac; Ozier, Owen (Becker Friedman Institute for Economics at the University of Chicago, 2022)
We examine the impact of enrolling in schools that employ a highly-standardized approach to education, using random variation from a large nationwide scholarship program. Bridge International Academies not...

Digital 2020: Kenya – DataReportal – Global Digital Insights - DataReportal (2020)

Kenya lauded for achieving 75% electricity access rate - Common Market for Eastern and Southern Africa (COMESA) (2021)

End education crisis in Northern Kenya - The Standard - Guleid, Mohamed (2021)

After COVID-19, let’s reimagine education in Kenya - Zaman, Maniza (2021)
Digital learning should be part of a basic package of essential services for every child

Kenya Partnership Compact. 2021 | Documents | Global Partnership for Education - Global Partnership for Education (2021)

KENYA GPE COVID 19 Learning Continuity in Basic Education Project - Global Partnership for Education (2020)

Alarm over teen pregnancies as Kenya ranked third worldwide | Nation - Maichuhie, Kamau (2022)

Low-tech personalised learning to improve girls' education in Kenya. - Jordan, K; Damani, K; Khagame, P; Mongeau, C; Mumbi, A; Myers, C; Njuguna, L; Otieno, J; Zhao, A (EdTech Hub and M-Shule, 2023)

Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

Human Development Reports - UNDP (2020)

Unlocking Literacy: Navigating Parental Engagement with Worldreader’s BookSmart in Kenya - Smith, Wendy; Nicolai, Susan; Kartha, Ashwati; Kimani, Olivia (EdTech Hub, 2024)
Globally, just one-third of 10-year-olds can read and understand basic written stories. Can EdTech and parental engagement change this? Read on to learn more.

Exploring the Landscape for Digital Education: Observations from Kenya, Nigeria, and Senegal - USAID (2022)

Impact of Covid-19 on the right to education In Kenya - Jelimo, Catherine (Right to Education Initiative, 2020)
On March 15, 2020, the Kenyan government abruptly closed all schools and colleges nationwide in response to COVID-19, disrupting nearly17 million learners countrywide. The closure of institutions not only affected learners and teachers but it also brought forth numerous economic and social issues, including interrupted and loss of learning, education exclusion, homelessness, nutrition and economic crisis, childcare challenges and increase in teenage pregnancy cases, financial cost implication to households, and sexual exploitation among others.

Application and program document for COVID-19 accelerated funding for Kenya - Global Partnership for Education (2020)

Concept on mapping technical and vocational educational and training data in Kenya - Ministry of Education (State Department for Vocational and Technical Training, 2021)

A spatial database of public primary day schools in western Kenya - Macharia, Peter M.; Moturi, Angela; Mumo, Eda; Snow, Robert W. (Harvard Dataverse, 2022)
Understanding the location of primary schools relative to population is important to contextualize the time, or distance, that students must travel...
Keywords: Other

Kenya: How Rogue Officials Inflated Enrolment, Used Ghost Schools to Steal Billions - Muchunguh, David (The Nation in Allafrica.com, 2021)

Technology Use for Teacher Professional Development in Low- and Middle-Income Countries: Recommendations for policy from a systematic review - D'Angelo, Sophia; Hennessy, Sara; Kreimeia, Adam; Koomar, Saalim; Cao, Lydia; McIntyre, Nora; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: Read; Teacher education and training; _r:AddedByZotZen

Report: The Impact of COVID-19 Across Africa - Elliott, Roxana (GeoPoll, 2020)
New report on coronavirus in sub-Saharan Africa including data from Kenya, Ghana, South Africa, Nigeria. COVID-19 and food security, economic impact.

Educational technology to improve capacity - integrating adaptive programmes in public schools in Kenya - Kaye, Tom (2021)

The Kenya Ministry of Education’s response to the COVID-19 pandemic: Case study - Gichuhi, Loise; Kallsta, Jane (UNESCO IIEP, 2022)

Pivoting in a Pandemic: eKitabu Provides Sign Language Video Content For Students in Kenya - eKitabu (2020)

Systems Implications for Core Instructional Support Lessons from Sobral (Brazil), Puebla (Mexico), and Kenya - Crouch, Luis (Research on Improving Systems of Education (RISE), 2020)
As this note was being written in April and May 2020, the Coronavirus pandemic was sweeping the world. Children were out of school. Researchers around the world are now estimating a severe learning gap due to loss of school attendance. While the first priority is getting children back to school safely, the discussion in this note regarding foundational learning is all the more relevant, as it is this kind of learning that is likely most affected. Key Points The case studies in this document highlight five tips that may be beneficial to other countries or situations: Focus on just a very few achievable indicators, foregrounding foundational learning, for a country emphasising learning. Use data to drive both initial “wake-up” and stock taking but also to support teaching as the process goes along. Emphasis on the teaching by the teachers who are already in place. Provide strong motivation through support that works. Use tight management so there is some degree of centralism and prescriptiveness as to pedagogy and other inputs, but after having iterated and adapted to context.

Educational Technology to Improve Capacity – Integrating Adaptive Education Programmes in Public School in Kenya - Kaye, Tom (Trust, Accountability and Capacity in Education System Reform, 2020)
Keywords: ___working_potential_duplicate

Kenya GPE 19 Learning Continuity in Basic Education Project - Implementation Status and Results Report - World Bank (2021)

Technology Enabled Learning in Kenya: KWA Ground Insights on Building Resilient Distance Learning Ecosystems - Otieno, Jennifer; Ward, Rebecca (IREX, 2022)
Keywords: ⛔ No INSPIRE recid found

A Dialogic Design-Based Research Partnership Approach: Developing Close-to-Practice Educational Technology Theory in Kenya - Major, Louis; Daltry, Rebecca; Rahman, Asad; Plaut, Daniel; Otieno, Mary; Otieno, Kevin (Global Perspectives on Teaching with Technology, 2024)
Design-based research (DBR) has promise for investigating educational technology in low- and middle-income contexts. However, DBR is implemented infrequently in such settings, highlighting a need for guidance on implementation. This chapter critically reflects on innovative DBR involving Kenyan teachers and research partners over two years. This focused on the iterative evaluation of a ‘digital personalised learning’ tool to improve its integration into classroom practice. This DBR promoted teacher-researcher engagement by adopting a dialogue-informed ‘intermediate theory building’ framework, bridging the theory-practice gap. Additionally, it enhanced inclusivity by broadening the concept of partnership through an ‘integrated’ approach. Lessons learned and practical implications are highlighted. Outcomes establish a novel foundation for applying DBR to enhance educational technology for marginalised learners.

Maintaining learning continuity during school closure: Community Health Volunteer support for marginalised girls in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Page, Ella; Naylor, Ruth; Jones, Charlotte; McAleavy, Tony (Education Development Trust, 2020)

Measuring the Impact of COVID-19 on Learning in Rural Kenya’ by Whizz Education (April 2021 - Whizz education (2021)

Teacher-AI Collaboration in Content Recommendation for Digital Personalised Learning among Pre-primary Learners in Kenya - Sun, Chen; Major, Louis; Daltry, Rebecca; Moustafa, Nariman; Friedberg, Aidan (L@S '24: Eleventh ACM Conference on Learning @ Scale, 2024)

An Improved Model for the Implementation of Web-Based Learning in Adult Secondary School Education in Kenya - Ng’ang’a, Ms Martha Muthoni; Kimani, Prof Stephen; Kimwele, Dr Michael W. (International Journal of Computer (IJC), 2020)
The development of technology, which evolves continuously, has led to the transformation of traditional courses into web-based courses. However, as these e-learning systems grow more complex, involving numerous users with different levels of need, there is a need to have web-based learning models that adequately address such users’ needs, taking into consideration their levels of expertise, access and ability to interact with such systems. Most of the existing models present the adult learners with difficulties, as most of them have to concentrate mostly on learning the technology rather than learning the desired content. Most of the difficulties arise from the web-based learning model configurations in use in the country. The majority lack features and capabilities of highly interactive, fast-paced multimedia-supported learning currently demanded by most learners and tutors. Therefore, the main aim of this research was to devise an improved model for implementing a web-based learning programme in adult secondary school education. After analysing the existing models and establishing their operational challenges, an improved model was proposed. The proposed model was statistically tested using sample data. The results showed that recognizing both technological and user attributes along the recognized theoretical frameworks was important in increasing the users’ behavioural inclination to use the improved model. Therefore, it is recommended that more sensitization to web-based learning should be implemented by the adult education department in the Ministry of Education among adult learners in the country. It is also recommended that system developers should find ways of incorporating additional features into the model without affecting its architecture and function. Finally, there is need for future studies on the causal antecedents of the constructs presented in this research model to provide more precise practical implications.
Keywords: Adult Learners; Model; Web Based Learning; ⛔ No DOI found

How Can Implementers Apply Digital Personalised Learning in Schools? - Plaut, Daniel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at digital personalised learning (DPL), a promising EdTech approach to improving learning outcomes, and consider how to implement this approach in school settings. We draw on work from EdTech Hub and other prominent researchers to first unpack the ‘basics’ of DPL implementation. These include the importance of teaching at the right level as a driver of DPL’s impact, and how DPL tools are applied in schools as supplementary learning and / or integrated into existing curricula. We also consider some of DPL’s technical requirements and achievements in improving learning outcomes. We then explore emerging insights about effective DPL implementation in schools, including the role of teachers as facilitators, the evidence behind student-device ratios, and the importance of coordinating DPL implementation with broader education system actors. Lastly, we look at areas that require further research, noting issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to DPL application in education systems. Keywords: digital personalised learning; DPL; implementation research; teaching at the right level; learning outcomes; education policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Integrating digital personalised learning into pre-primary classroom practice: A teacher-researcher multiple-case study partnership in Kenya - Daltry, Rebecca; Major, Louis; Otieno, Mary; Otieno, Kevin; Jordan, Katy; Moustafa, Nariman (Education Sciences, 2025)
Keywords: ⛔ No DOI found

Are Our Children Learning? The status of remote-learning among school-going children in Kenya during the Covid-19 Crisis - Uwezo (Usawa Agenda, 2020)

Implementing Parental Empowerment and Engagement Strategies in Times of Crisis: Experiences from Regional Educational Learning Initiative members in Kenya - Angoye, James (Regional Education Learning Initiative Africa, 2021)

Toward a holistic approach to EdTech effectiveness: Lessons from Covid-19 research in Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone - Nicolai, Susan; Jordan, Katy; Adam, Taskeen; Kaye, Tom; Myers, Christina (International Journal of Educational Development, 2023)

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 3: Skills taxonomy - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the third of five reports on the development of a proof of concept for the Hub and describes our observations during the creation of a skills taxonomy. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Distanced and Disadvantaged: A Study on the Effects of COVID-19 on Education for Learners with Disabilities in Kenya, October 2020 - Angoye, James; Mbari-Kirika, Irene; Walker, Bruce; Kavua, Martin (inABLE.org, 2020)

Is 2020 a lost academic year? The impact of COVID-19 on education in eastern Africa: a case study of Kenya - Cordeiro, Vanessa Cezarita (Humanium, 2020)
Despite national efforts and strict measures designed to curb the spread of the virus, the country continues to suffer from the knock-on effects of the pandemic.

Assessment of parent’s engagement in implementation of competency-based curriculum in private primary schools in Tharaka South Sub-County of Tharaka-Nithi County, Nithi County, Kenya - Njeru, Atanasia Ikoore; Kirimi, Josephine (European Journal of Education Studies, 2023)
Education is a shared responsibility and all stakeholders need to understand and appreciate what is being done and what is required of them to make meaningful contributions to the process. Because the Competency-Based Curriculum shifted its focus from teaching-centric to collaborative-centered, parents are important stakeholders for its successful implementation. Therefore, empowering and engaging a parent in the learning process is essential to the learner’s growth and development. The study examined parents’ engagement in CBC implementation. This study specifically aimed to determine parents’ engagement in the implementation of Competency-Based Curriculum in private primary schools in Tharaka South Sub-County of Tharaka-Nithi County. To get this, the researcher went to private primary schools in Tharaka South Sub County to observe how parents are embracing CBC and randomly selected some parents for interviews, teachers, and head teachers to fill out questionnaires. The study adopted a descriptive survey design where the targeted population was drawn from the 30 private schools in the sub-county. The study targeted 528 respondents. 66 respondents were sampled: 42 parents, 18 teachers and 6 head teachers. Simple random sampling was then used to select the participant. The study conducted a pretest study in 3 private primary schools for the purpose of validating the research instruments. Data was collected using questionnaires for head teachers and teachers and interview schedules for parents. The validity of the research instruments was determined through expert judgment whereas the reliability of the questionnaires was determined through a Cronbach’s alpha coefficient of 0.7982 was obtained. Qualitative data was analyzed thematically whereas quantitative data was summarized using percentages, mean, standard deviation and frequencies were used. This was facilitated by the Statistical Package for Social Sciences (SPSS) Version 21. The study established a significant relationship between the parent’s literacy and the implementation of CBC with a significance value of p=0.000<0.05. The study concluded that the implementation of CBC is greatly challenged by a lack of sensitization on the implementation of the CBC and perceived CBC as expensive, demanding and time-consuming. Thus, recommended that the private schools get more time with their parents to sensitize them on the CBC implementation and get to know their role in the academic performance of their children and also try to change their perception of CBC as expensive, demanding and time-consuming.  Article visualizations:
Keywords: competency-based curriculum; curriculum implementation; parent’s engagement

Overview of emerging country-level response to providing educational continuity under COVID-19: What’s working? What isn’t? - Joynes, Chris; Gibbs, Emma; Sims, Kate (2020)
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Teaching literacy to youth in Dadaab - Rich, Sam (eLimu, 2020)
According to what statistics you use, Dadaab refugee camp is the fifth or sixth biggest city in Kenya. In the middle of 2017, its population was 250,000 and Norwegian Refugee Council (an international humanitarian organisation that focuses on displaced people) was running…

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Eneza Education website - Eneza Education (Eneza Education, 2020)
Eneza Education is an ed-tech company that provides curriculum aligned revision material in all subjects for primary and secondary learners on any device. Our virtual tutor provides access to curriculum-aligned ... Read More

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?”  As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Covid-19 and EdTech in Africa: A Country-Level Review Based on eLearning Africa Data - Damani, Kalifa (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

The use of 'building blocks' to develop digital platforms for education in sub-Saharan Africa - Adam, Taskeen; El-Serafy, Yomna; Podea, Marius; Haßler, Björn (EdTech Hub, 2021)
We set out to investigate the existing and potential use cases of open-source, modular ‘building blocks’ to build digital platforms for education in sub-Saharan Africa (SSA). Building blocks fall into two main categories: teaching and learning (e.g., learning management systems) and education system management (e.g., data collection tools).
Keywords: _EdTechHub_Output; _MELA_seen

Education during the COVID-19 crisis: opportunities and constraints of using EdTech in low-income countries - David, Raluca; Pellini, Arnaldo; Jordan, Katy; Philips, Toby (Zenodo, 2020)
Key points: Technology can help mitigate the effects of the educational crisis and closures of schools, but ed-tech is not a silver bullet and governments need to have realistic expectations about what it can achieve The digital divide means that internet and mobile network access varies greatly in middle- and low-income countries Governments can provide immediate support by informing teachers about simple grassroots platforms where they can share their own ed-tech solutions Educational TV and radio broadcasts in combination with SMS are effective communication channels between educators and students when the internet connectivity is poor or not available It will be important for education authorities to begin planning how in 12-months’ time they will diagnose and treat the learning gaps that have emerged during the crisis.
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodoETH; covid-19; crisis education; distance education; education; education policy; educational technology; emergency education; pandemic education; school closures; schools

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (#SaveOurFuture, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 5: Final report - Groeneveld, Caspar; Michels, Guillaume; Kaye, Tom (EdTech Hub, 2022)
In 2021, the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE), and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fifth and final report on the development of a proof of concept for the Regional Learning Hub. We recommend beginning with this document and then moving to any of the remaining four reports, depending on your interest: Inception report; User research; Skills taxonomy; Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Ed-Tech landscape and challenges in Sub-Saharan Africa - Adeniran, Adedeji; Adedeji, Abdulfatai; Nwosu, Emmanuel; Nwugo, Emmanuel; Nnamani, Great (Southern Voice, 2023)
This study examines the adoption of education technology (ed-tech) in primary and secondary education in 10 sub-Saharan African countries: Nigeria, South Africa, Sierra Leone, Uganda, Kenya, Tanzania, Cameroon, Benin, Malawi, and Senegal. The study assesses the development and implementation of ed-tech policies and programmes in the region, exploring how far ed-tech has advanced learning outcomes, improved access, and reduced education inequalities within and between countries in sub-Saharan Africa.

Teacher professional development and coaching in low-income countries: Practical considerations for the use of technology. - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This third paper offers a range of practical considerations.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:o; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Session 5: How can I use EdTech to ensure that students are provided with quality educational content at the right level? - Mazari, Haani; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 4: Content curation - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fourth of five reports on the development of a proof of concept for the Hub and describes our observations during content curation. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Report of Case Studies on Responses to the Covid-19 Pandemic in Africa’s Educational Systems - Kiru, Elisheba; Ochieng, Vollan; Wawire, Brenda; Habiamana, Oliver; Ngware, Moses (APHRC, 2023)
This report presents case studies from seven African countries (i.e., Burkina Faso, Kenya, Malawi, Mali, Mozambique, Niger, and Nigeria) that implemented programs and innovations in response to the effects of the COVID-19 pandemic on the education systems. The report provides insights into building resilience within Africa’s education systems for the future. The case studies fill existing knowledge gaps on promising practices and add value to discussions on the contextual drivers that facilitated the implementation of the interventions, including active government involvement in mobilizing and supporting the initiatives. The programs include the PRONAE national school feeding program in Mozambique, the online teacher professional development program in Kenya, teacher training in Niger, back-to-school campaigns in Malawi, basic education training in internally displaced camps in Burkina Faso and Niger, and initiatives addressing sexual and gender-based violence in Mali. The case studies also seek to examine the extent to which the interventions addressed gender, equity, and inclusion. For the Global Partnership for Education (GPE) partner countries, these case studies provide valuable information regarding the operations of education systems and the well-being of learners.

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Guidance Note 3 Digital technologies and girls’ education From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

EdTech for Girls' Education: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; D'Rozario, Jonny; Thinley, Sangay; Mazari, Haani; Hinks, Jessica (EdTech Hub, 2025)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for girls in Southeast Asia. The review summarises how EdTech is currently being used with girls in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech for girls' education. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for girls, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for girls. An output of the EdTech Hub, https://edtechhub.org/

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Critical perspectives on the use of technology with refugees and displaced communities: The case of Dadaab - Leomoi, Ochan (Journal of Interactive Media in Education, 2025)
Dadaab Refugee Complex hosts refugees from the Horn of Africa and the Great Lakes region. According to a UNHCR (2023) report, at 31 January 2023 Dadaab refugee camps were host to a total population of 233,828 registered refugees and asylum seekers, representing 41% of the total recognized forcibly displaced people in Kenya. This paper will explore Dadaab as the context for connected learning in addition to the author’s first-hand accounts. The author provides a reflexive account of the perspectives of refugees in Dadaab refugee camps and Dadaab host-communities on the role of higher education for individual and social transformation, and how technology could be embraced to leverage learning despite challenges to the access and use of the internet, and computers. In this paper, the author makes a reflexive account of the role of education in transforming refugee learners and communities, and how technology was employed, albeit with challenges, to connect Dadaab with other higher education institutions within and beyond Kenya’s boundaries. The author is further concerned with how technology in higher education in crisis contexts is conceived as the agent that builds networks of scholars, generates connections for development, and promotes exchange of knowledge and ideas among students and faculty across all geographical borders.

Teacher professional development and coaching in low-income countries: An evidence-informed conversation - Haßler, Björn; Moss, Caitlin (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This first paper offers a broad overview.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:m; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

How to Design EdTech Programmes That Lead to Gender-Transformative Change - Samuels, Fiona; Leon-Himmelstine, Carmen; Marcus, Rachel; Myers, Christina (EdTech Hub, 2022)
This paper outlines how EdTech programming can adopt a gender-transformative approach to improve gender equity in access and learning outcomes. It explains what the term ‘gender-transformative change’ means, and why it is needed. Some key dimensions of gender-transformative approaches in the specific context of EdTech initiatives are outlined, looking at how different approaches can enhance access to education and learning opportunities and improve outcomes, and challenge discriminatory gender norms and stereotypes. Based on a desk review of grey and published materials, this paper then presents and discusses insights from the approaches taken by four EdTech programmes. Keywords: EdTech; gender-transformative; country case studies; education; girls’ education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia - Vijil, Alejandra; El-Serafy, Yomna; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2024)
This report provides a landscape analysis of available data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia. Digital data collection has the potential to facilitate cost-effective, adaptable, timely and reliable data to inform decision-making. The value proposition of these tools, as opposed to paper-based data collection, is that they have the potential to save valuable time and resources, minimise errors, and facilitate the sharing of results. To develop this report, we reviewed 50 available tools, of which we reviewed four in depth, considering their uses, features, and challenges. This report offers key takeaways on the potential advantages and limitations of using digital data collection tools in the education sector in sub-Saharan Africa and South Asia. Key words: data collection, data visualisation, education, sub-saharan africa, south asia, landscape analysis An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Research on the response to COVID19 - Haßler, Björn; Fitzpatrick, Rachael (BE2, 2020)
Presentation given at BE2, 2020-10-06.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _yl:u; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Learning Curve: Progress in the Replication Crisis - Angrist, Noam; Cullen, Claire; Ainomugisha, Micheal; Bathena, Sai Pramod; Bergman, Peter; Crossley, Colin; Letsomo, Thato; Matsheng, Moitshepi; Panti, Rene Marlon; Sabarwal, Shwetlena; Sullivan, Tim (AEA Papers and Proceedings, 2023)
We present detailed monitoring data across a five-country randomized trial of phone-based targeted tutoring–one of the largest multicountry replication efforts in education to date. We study an approach shown to work in Botswana and replicated in India, Kenya, Nepal, the Philippines, and Uganda. While the existing literature often finds diminishing effects as proof-of-concept studies are replicated and scaled, we find the opposite: implementation fidelity (the degree of targeted educational instruction) improves across replications and over time. This demonstrates that replication is not intractable; rather, equipped with mechanisms to learn from experience, organizational “learning curves” can enable effective replication and scale-up.

Girls’ Education and EdTech: A Rapid Evidence Review - Webb, Daniel; Barringer, Katie; Torrance, Rebecca; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of technology in supporting girls’ education in low and middle-income countries (LMICs). The RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread global shutdown of schools. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations to the continuation of schooling caused by COVID-19. Established approaches to maintaining continuity of education for the most marginalised have particular salience during this period because of the significant increase in the number of students at risk of disruption. Research consistently shows that while education across the board is negatively affected by crisis situations, the schooling of girls is disproportionately impacted. The RER aims neither to advocate nor discourage the use of technology in girls’ education in response to the present COVID-19 pandemic, but rather to provide an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential role of technology in delivering education for girls.
Keywords: L:English UXZJW5DR; L:Gender and education; LP: English; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; ⛔ No DOI found; ⛔ No INSPIRE recid found

Building back better to avert a learning catastrophe: Estimating learning loss from COVID-19 school shutdowns in Africa and facilitating short-term and long-term learning recovery - Angrist, Noam; de Barros, Andreas; Bhula, Radhika; Chakera, Shiraz; Cummiskey, Chris; DeStefano, Joseph; Floretta, John; Kaffenberger, Michelle; Piper, Benjamin; Stern, Jonathan (International Journal of Educational Development, 2021)
We model learning losses due to the COVID-19 pandemic and the potential for cost-effective strategies to build back better. Data from Early Grade Reading Assessments in Ethiopia, Kenya, Liberia, Tanzania, and Uganda suggest half to over a year’s worth of learning loss. In modeling losses over time, we found that learning deficits for a child in grade 3 could lead to 2.8 years of lost learning by grade 10. While COVID-19 has stymied learning, bold, learning-focused reform consistent with the literature reviewed in this paper—specifically reform on targeted instruction and structured pedagogy—could improve learning even beyond pre-COVID-19 levels.
Keywords: COVID-19; Education; Foundational skills; Learning loss; Recovery

Impact de la pandémie de COVID-19 sur l’éducation en Afrique et incidence sur le recours aux technologies: Sondage sur l’expérience et les opinions des éducateurs et spécialistes de technologies - eLearning Africa; EdTech Hub (2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

Education during the COVID-19: crisis Opportunities and constraints of using EdTech in low-income countries - Jordan, Katy; David, Raluca; Phillips, Toby; Pellini, Arnaldo (Revista de Educación a Distancia (RED), 2021)
The Covid-19 pandemic has ushered in a period of educational disruption on an unprecedented scale. During this time of crisis, education will not be business as usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t st op — but they could be helped by the right EdTech tools. However, the digital divide means that internet and mobile network access varies greatly in middle and low - income countries. In this discussion paper, we explore some of the key constraints of using EdTech at scale to support education in low - income countries at a time of crisis, and highlight the opportunities that have so far emerged, in a rapidly - changing context. We draw upon evidence and examples to inform policy and programming decisions, moving from the initial emergency response to building resilience in the longer term, and planning to diagnose and treat the learning gaps that have emerged during the crisis.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; países de bajos ingresos

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Unlocking data to tell the story of education in Africa: webinar summary & synthesis - Adam, Taskeen; Agyapong, Samuel; Asare, Samuel; Heady, Lucy; Wairimu, Wacharia; Mjomba, Renaldah; Mugo, John; Mukiria, Faith; Munday, Gemma (Zenodo, 2020)
[No description available.]
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Remote Supervision Options for School Quality Assurance Officers: Recommendations for a cost-effective and rapid develop-and-test process - Beoku-Betts, Iman; Ampofo, Rudolph; Haßler, Björn (EdTech Hub, 2024)
The Sierra Leone Secondary Education Improvement Programme II (SSEIP II) is a five-year programme funded by the UK Foreign, Commonwealth and Development Office (FCDO) to support the Ministry of Basic and Senior Secondary Education (MBSSE) to improve learning outcomes for students at secondary level and to increase the enrolment, retention and well-being of girls and children with disabilities in school. Part of the programme includes exploring the use of different digital tools for School Quality Assurance Officers (SQAOs), including tools for remote visits. In December 2022, the EdTech Hub collaborated with the Government of Sierra Leone and implementing partners of the Leh Wi Lan programme (continued under SSEIP II) to better understand what factors affect the variability in the activity levels of SQAOs and the level of engagement with digital tools by school principals. Based on the findings of this research, the SSEIP II project will look at supporting the MBSSE to formalise remote supervision options for the SQAOs, particularly for those with remote clusters. As part of this work, this report focuses on recommendations for how SQAOs can conduct remote school visits, particularly for schools in hard-to-reach areas.An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech to Support Blended Learning in Mozambique: A curated list of EdTech interventions - Flam, Rebekka; Ramesh Vasudevan, Sharanya; Coutrim, Erica (EdTech Hub, 2024)
This document was produced in response to a request from the UNICEF Mozambique country office submitted to the EdTech Hub Helpdesk in November 2023. The UNICEF team requested a curated list of blended learning approaches and resources that are relevant to the Mozambique context, with a special focus on resources that are implemented or sourced from the Eastern and Southern Africa region. In response, the EdTech Hub Helpdesk has created this report to provide contextual and background information on the blended learning landscape in Eastern and Southern Africa, with a specific focus on Mozambique, along with a list of resources on blended learning. Keywords: blended learning; hybrid learning; Africa; Mozambique An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Teacher Motivation: Exploring non-financial incentives in school-based teacher professional development in Tanzania - Anonymised for Peer Review (EdTech Hub, 2025)
High-income countries often use external incentives such as remuneration, professional pathways or accreditation to motivate teachers to engage in professional development. This paper reflects on the challenges of engaging teachers in school-based professional development in resource-scarce education environments where the use of such incentives is not feasible and explores practical strategies to motivate their engagement. In such contexts, where qualified teacher status and promotion are not tied to engagement in professional development, other means for encouraging teachers to take up professional learning opportunities are paramount. In this two-year, iterative, design-based implementation research study of a national teacher professional development initiative in Tanzania, non-financial incentives were tested in eight rural schools. Findings show that completion certificates motivated teachers; achievement certificates had mixed results due to doubt around the fairness of the peer-review process. Additionally, teachers were intrinsically motivated by other changes in the programme such as access to relevant digital modules which allowed for teacher agency, and by increased collegial relationships and collaboration. Keywords: teacher motivation; school-based teacher professional development; design-based implementation research; Tanzania, non-financial incentives; intrinsic and extrinsic motivation An output of the EdTech Hub, https://edtechhub.org/
Keywords: Hide; _r:AddedByMyEducationEvidence

TCPD in Tanzania: Design-Based Implementation Research Cycle 1 Recommendations Policy Brief - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Frederick; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the first cycle of the DBIR carried out between September and December 2022. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; tanzania; communities of learning An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

EdTech Policy Rapid Scan for Sub-Saharan Africa - Flam, Rebekka; Oyedele, Oluwatomisin (EdTech Hub, 2025)
This rapid scan presents a curated list of EdTech policies in sub-Saharan Africa, compiled in response to a request from the World Bank. Based on desk research from mid-2024, it highlights that most policies predate COVID-19, with few new ones emerging post-2020. Many countries lack dedicated EdTech policies, instead relying on broader ICT or education strategies. Common themes include digital infrastructure, distance learning, and teacher training, while gaps remain in support for marginalised learners. The report provides an overview of existing policies, while the highlighted trends offer insights for future policy development. Keywords: EdTech policy; education policy; sub-Saharan Africa; EdTech governance; digital learning; digital infrastructure An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Experiment Types for EdTech - Rahman, Asad; Carter, Alice; WambûiKuria, Catherine; Mbugua, Ciku; Simpson, Lea; Kably, Nathan (EdTech Hub, 2022)
An EdTech Hub sandbox fast-tracks promising EdTech interventions by providing funding, tools, and access to evidence. It provides a space for partners to test and grow ideas in conditions of uncertainty. Since 2020, EdTech Hub has worked with partners in eight countries to test and grow EdTech based on our sandbox methodology. When testing and growing EdTech, this tool provides a non-exhaustive list of ways to design and run experiments. Keywords: sandbox; lean startup; lean impact; experiments; validation; prototype An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Artificial Intelligence and Education Systems in 2035: Fourteen trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in artificial intelligence (AI) that might occur over the next 10 years. It begins by capturing fourteen trends, relating to AI that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Guidance on Community Mobilisation for Girls’ Education - AlSheikh Theeb, Thaer; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _r:AddedByZotZen

Session 4: How can I rapidly upskill my large teacher workforce? - Koomar, Saalim; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

Can A/B Testing at Scale Accelerate Learning Outcomes in Low- and Middle-Income Environments? - Friedberg, Aidan (Springer Nature Switzerland, 2023)
On current trends the world will fail to reach the objectives set in the UN’s Sustainable Development Goals for Education by 2030 or even within the 21st century. Changing this trend will require a significant acceleration in learning outcomes. Digital personalised learning (DPL) tools are a potentially cost-effective intervention that can contribute to this acceleration. In particular, the continuous experimentation afforded by these tools through software A/B testing, has considerable potential to create compounding improvements in learning outcomes. This paper provides an overview of EIDU, an educational platform combining student focused DPL content with digital structured pedagogy programmes in public pre-primary schools in Kenya. Collection of student’s longitudinal unsupervised assessment data at scale creates the possibility of learning outcome focused A/B testing. This is a novel contribution to the development and research field as up until now this type of capability has largely been confined to students in high-income environments.

Overview of emerging country-level response to providing educational continuity under COVID-19: What are the lessons learned from supporting education for marginalised girls that could be relevant for EdTech responses to COVID-19 in lower- and middle-income countries? - Naylor, Ruth; Gorgen, Kristine (EdTech Hub, 2020)
Keywords: COV:COVID and reopening of schools; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Summary: EdTech for Girls’ Education - A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Hinks, Jessica; D'Rozario, Jonny; Thinley, Sangay (EdTech Hub, 2024)
This document is a summary of a Rapid Evidence Review on EdTech for Girls' Education produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Perceptions of autism spectrum disorder among the Swahili community on the Kenyan coast - Greer, J. M. H.; Sood, S. S. M.; Metcalfe, D. R. (Research in Developmental Disabilities, 2022)
Background In high-income and Western societies there is great understanding and awareness of autism spectrum disorder (ASD); however, for many low-middle income countries, research and knowledge is notably lacking. In Africa, there is a growing prevalence of ASD due to increased diagnosis, yet it is still a poorly understood condition. Aims Emerging literature has emphasised how cultural and societal beliefs underpin the level of understanding of ASD, and which typically results in lack of awareness and acceptance. As such it is important to investigate the cultural perceptions towards ASD within low-middle income communities of African culture, to further understand the challenges and barriers individuals with ASD face. The aim of the current study was to probe participants from the Swahili community, on the coast of Kenya, of their cultural views towards ASD. Method Semi-structured interviews were conducted with seven participants, and the data analysed using thematic analysis. Results Three key themes developed from the data; stigma, lack of awareness, and Government responsibility. Conclusion Cultural perceptions negatively impacted awareness and are exacerbated by lack of directive from the Government in providing appropriate diagnostic and educational support.
Keywords: ASD; Government responsibility; Lack of awareness; Stigma; Swahili community

Perceptions of autism spectrum disorder among the Swahili community on the Kenyan coast - Greer, Jo; Sood, S. S. M.; Metcalfe, Dale (Research in Developmental Disabilities, 2022)
Background: In high-income and Western societies there is great understanding and awareness of autism spectrum disorder (ASD); however, for many low-middle income countries, research and knowledge is notably lacking. In Africa, there is a growing prevalence of ASD due to increased diagnosis, yet it is still a poorly understood condition. Aims: Emerging literature has emphasised how cultural and societal beliefs underpin the level of understanding of ASD, and which typically results in lack of awareness and acceptance. As such it is important to investigate the cultural perceptions towards ASD within low-middle income communities of African culture, to further understand the challenges and barriers individuals with ASD face. The aim of the current study was to probe participants from the Swahili community, on the coast of Kenya, of their cultural views towards ASD.Method: Semi-structured interviews were conducted with seven participants, and the data analysed using thematic analysis. Results: Three key themes developed from the data; stigma, lack of awareness, and Government responsibility. Conclusion: Cultural perceptions negatively impacted awareness and are exacerbated by lack of directive from the Government in providing appropriate diagnostic and educational support.
Keywords: ASD; Government responsibility; Lack of awareness; Stigma; Swahili community; ⛔ No INSPIRE recid found

Integrating ICT into schools in Sub-Saharan Africa: from teachers’ capacity building to classroom implementation - Agyei, D. D (Education and Information Technologies, 2021)
This study followed up on a selected cohort of 4945 Science, Technology, English and Mathematics (STEM) teacher participants from six Sub-Saharan African countries namely: Kenya, Tanzania, Uganda, Ethiopia, Ghana and Nigeria. The teachers were involved in an instructional digital professional development programme targeted at building their capacity to embed ICT into school organizational and curriculum practices. This study sought to evaluate the impact of the ICT- instructional professional development programme in relation to the quality and the extent of the teachers’ transfer of the programme’s ideas from capacity building to classroom instructional practices. Data for the study were collected using semi-structured survey instrument and diaries kept to maintain records of activities and events during the period of implementation. Findings revealed that the teachers expressed general satisfaction with content and processes of the training programme; however, essential conditions to support transfer of the training’s ideas to school level seemed not adequate during the period of implementation. Implications for effective professional development in integrating ICT into school organization and curriculum practices that have sustainable impact on teaching and learning particularly in Sub-Saharan regions and similar contexts are discussed.

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Guidance Note 7 Ensuring resilient connectivity From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Session 3: How can I develop an aligned and actionable EdTech strategy - Wyss, Natalie; Mbugua, Wanjiku; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Teacher professional development and coaching in low-income countries: Overarching considerations for the use of technology - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This second paper offers a wider perspective with some overarching considerations.
Keywords: C:Low-income countries; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
Keywords: ⛔ No INSPIRE recid found

Deploying an e-learning Environment in Zanzibar: Digital Content Curation - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank approached EdTech Hub (the Hub) to explore the feasibility of implementing a Virtual Learning Environment (VLE). The MoEVT, the World Bank and the Hub agreed that the Hub would work with the MoEVT to develop the following 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of the e-learning system. This document addresses the second part of the request and is an elaboration of the digital content selection, curation, and adaptation process suggested in the first report. However, this document is a stand-alone piece that does not require familiarity with any of the other deliverables.
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

Combining school-catchment area models with geostatistical models for analysing school survey data from low-resource settings: Inferential benefits and limitations - Macharia, Peter M.; Ray, Nicolas; Gitonga, Caroline W.; Snow, Robert W.; Giorgi, Emanuele (Spatial Statistics, 2022)
School-based sampling has been used to inform targeted responses for malaria and neglected tropical diseases. Standard geostatistical methods for mapping disease prevalence use the school location to model spatial correlation, which is questionable since exposure to the disease is more likely to occur in the residential location. In this paper, we propose to overcome the limitations of standard geostatistical methods by introducing a modelling framework that accounts for the uncertainty in the location of the residence of the students. By using cost distance and cost allocation models to define spatial accessibility and in absence of any information on the travel mode of students to school, we consider three school catchment area models that assume walking only, walking and bicycling and, walking and motorized transport. We illustrate the use of this approach using two case studies of malaria in Kenya and compare it with the standard approach that uses the school locations to build geostatistical models. We argue that the proposed modelling framework presents several inferential benefits, such as the ability to combine data from multiple surveys some of which may also record the residence location, and to deal with ecological bias when estimating the effects of malaria risk factors. However, our results show that invalid assumptions on the modes of travel to school can worsen the predictive performance of geostatistical models. Future research in this area should focus on collecting information on the modes of transportation to school which can then be used to better parametrize the catchment area models.
Keywords: Catchment area models; Disease mapping; Missing locations; Model-based geostatistics; Prevalence; School survey

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

The Use of Virtual Learning Environments and Learning Management Systems During the Covid-19 Pandemic - McBurnie, Chris (EdTech Hub, 2020)
This technical note aims to inform the use and development of virtual learning environments (VLE) in educational responses to the current health crisis. It considers the advantages and disadvantages of a number of existing VLEs and includes guidance on selecting an appropriate VLE.
Keywords: COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

SUMMARY Learning through the crisis: Helping decision-makers around the world use digital technology to combat the educational challenges produced by the current COVID-19 pandemic - Traxler, John; Scott, Howard; Smith, Matt; Hayes, Sarah (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Using EdTech in Response to Climate Emergencies in Pakistan - Hayat, Amal; Mazari, Haani; Aslam, Nawaz (EdTech Hub, 2025)
This policy brief explores how EdTech can support a climate-resilient education system, drawing on insights from stakeholder consultations and EdTech Hub's research on learning continuity in response to climate emergencies following the 2022 Pakistan floods. While recovery efforts often focus on restoring physical infrastructure, we argue that a shift to long-term resilience against climate emergencies can be supported by strategic and contextually relevant use of EdTech. The brief highlights the importance of addressing the evolving needs of learners and teachers across all phases of emergencies through preparedness measures and cross-sectoral collaboration. Keywords: Pakistan floods; climate resilience; EdTech; Education in emergencies; South Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Cost-Effectiveness and EdTech: Considerations and case studies - Chuang, Rachel; Burnett, Nicholas; Robinson, Elizabeth (EdTech Hub, 2021)
The answer to the question ‘What is cost-effective EdTech?’ is highly nuanced, as it depends on the choice of the initiative, its design, implementation, intended audience, and how the local context is addressed. We compiled select case studies that examine how EdTech was used in cost-effective and less cost-effective ways. An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

EdTech Horizon Scan: Rapid scan of online safety in education - Mazari, Haani; Kaye, Tom (EdTech Hub, 2022)
This EdTech Horizon Scan examines the issue of online safety in digital education — why it should be prioritised, how it is currently being approached, and its potential to become central to education design in low- and middle-income countries. Given that the internet has no borders, there is much to be done to address online safety in all parts of the world — high-income and low- and middle-income countries alike. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

A Literature Overview of Accountability and EdTech: Recommendations for Using Technology to Improve Accountability in Educational Systems from Ghana and Other LMICs. - McIntyre, Nora; Sabates, Ricardo; Eberhardt, Molly Jamieson (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

What steps are being taken to reach the most disadvantaged students during the period of Covid-19 school closure? - McAleavy, Tony; Joynes, Chris; Gibbs, Emma; Sims, Kate (Education Development Trust, 2020)
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Advancing Learning Outcomes for Transformational Change III - African Population and Health Research Center (African Population and Health Research Center, 2021)

Evaluating the Learner Experience of the TCPD Learning Management System for Primary School Teachers in Tanzania - Kondoro, Aron; Maro, Salome; Mtebe, Joel; Simmons, Hannah; Komba, Aneth (2025 IST-Africa Conference (IST-Africa), 2025)

How Can Decision-Makers Assess EdTech Interventions for Cost-Effectiveness to Enable Better Investments? - Plaut, Daniel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how decision-makers should consider cost-effectiveness when contemplating investing in EdTech programmes. Cost-effectiveness is a critically important consideration for anyone planning investments in EdTech, but it is also a complex one, which requires understanding the total cost of an intervention and comparing it against the likely impact on education. We draw on work from EdTech Hub and other prominent researchers to distil key practical insights for decision-makers on how to apply cost-effectiveness analysis to their decision-making. Practical considerations include recommendations on gathering the right data for analysis; ensuring cost calculations are holistic; leveraging existing frameworks and tools for cost and impact calculations; and ensuring that comparisons are made against non-tech interventions as well as the broader resource envelope available for education to determine affordability in a given context. Finally, we explore areas where additional work is needed, including an increased understanding of the challenges faced by decision-makers in considering cost-effectiveness and the need for greater transparency and accountability in cost-effectiveness analysis in the sector. Keywords Cost-effectiveness; EdTech; education policy; total cost of implementation; affordability; Learning-Adjusted Years of Schooling An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Education in Conflict and Crisis in 2035: Twelve trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in the increase in global conflict and crises that might occur over the next 10 years. It begins by capturing twelve trends, relating to conflict and crisis, that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo, Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Evidence Coaching Handbook - Rahman, Asad (EdTech Hub, 2024)
This handbook captures EdTech Hub's approach to providing evidence coaching on the EdTech Hub Evidence-Led Entrepreneurship Course. Individuals and organisations who support EdTech entrepreneurs to scale their products impactfully (e.g., accelerators, entrepreneurship programmes, funders) can all provide evidence coaching to entrepreneurs. This Handbook is for anyone working within an EdTech startup, or an entrepreneur who wants to better apply evidence to key decisions. By sharing EdTech Hub’s approach and process for evidence coaching, we hope to nurture a more evidence-led EdTech entrepreneurship ecosystem, leading to more EdTech products that scale sustainably, and help children to read, write, and count. The Handbook contains EdTech Hub’s five-step process for generating and applying evidence as a startup, with specific tools we used along the way. The process is a guide for others to adapt and tailor to their unique context and challenges. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Delivering Remote Learning Using a Low-Tech Solution: Evidence from an RCT during the Covid-19 Pandemic - Islam, Asad; Wang, Liang Choon; Hassan, Hashibul (EdTech Hub, 2022)
During the prolonged school closure due to the Covid-19 pandemic, many children in rural Bangladesh were missing out on formal education. What is more these children had limited access to distance learning modalities such as the internet, television, and radio. To counteract this poor access, this study used the widely accessible modality of mobile phones to deliver a set of audio lessons to primary school students using Interactive Voice Response (IVR). These lessons were developed using the Interactive Radio Instruction (IRI) method. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

How Can EMIS be Designed and Implemented in Ways That Make Them Used and Useful? - Adam, Taskeen; Mitchell, Joel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at education management information systems (EMIS). EMIS are pivotal in educational administration, facilitating the digitisation of processes and data to enable informed decision-making. However, persistent challenges impede their effectiveness. We examine why it is vital to consider how EMIS are designed and implemented, particularly with regard to the needs and contexts of low- and middle-income countries (LMICs). We consider constraints in technical capacity, limited funding, and insufficient user engagement. We identify concrete, evidence-based recommendations for how to make EMIS useful and used more frequently based on current and recent research. To enhance EMIS efficacy, there is a need to underscore utility and usability, ensuring the collection of pertinent data and user-friendly interfaces. Furthermore, the social implications of EMIS data on individuals and communities must be considered in order to meet their needs. We also explore areas for further consideration and include lists of resources relevant to EMIS and questions and solutions to consider. Keywords: education management information systems (EMIS); low- and middle-income countries (LMICs); user-centred design; evidence-based decision-making; EdTech; educational administration. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

The Use of Interactive Whiteboards to Support Refugee Learning - Ramesh Vasudevan, Sharanya; Handigol, Apoorva (EdTech Hub, 2025)
This EdTech Hub rapid scan outlines the efficacy of interactive whiteboards (IWBs) to better understand the potential impact of investment in the digitisation of teaching and learning materials to enhance access to education and learning for refugee children. The focus is on research that can highlight any evidence on the efficacy of interactive whiteboards in low- and middle-income country (LMIC) contexts characterised by high numbers of school-age refugees, with Turkey as a key case study. The scan highlights important and valid considerations that can be applied to broader learnings around IWBs. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Harnessing EdTech for Neurodivergent Learners in LMICs: A Rapid Evidence Synthesis - Layachi, Aida; Plaut, Daniel (EdTech Hub, 2025)
As neurodivergent learners continue to face multifaceted challenges that affect their education, education systems, environments, and practices have struggled to address their needs adequately. This rapid evidence synthesis explores the current state of evidence regarding the use of educational technologies (EdTech) for neurodivergent learners in low-and middle-income countries (LMICs). The review was conducted in two phases to offer complementary insights on the topic. The first phase presents the findings regarding the use of EdTech for neurodivergent learners in LMICs. The second phase expands the focus, offering evidence and examples that extend beyond LMICs, providing a global perspective on how EdTech could be applied and adapted to LMICs to address different challenges faced by neurodivergent learners. The holistic framework for EdTech for neurodivergence presented in this synthesis provides insights and recommendations regarding the potential of EdTech in optimising systems, environments, and education practices. Keywords: EdTech, Neurodivergence, LMICs, holistic framework, learners An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Should we paint all classroom roofs white to improve learning in Tanzania? - Proctor, Jamie (2022)
A growing literature base has developed from Global North contexts, showing a clear link between classroom temperature and student learning outcomes. However, very little evidence shows how this impact translates to low- and middle-income countries (LMICs), where average classroom temperatures are often high. The hypothesis for the research was that classroom temperatures in Tanzania are high and that a white-paint-cool-roof intervention would help mitigate these high temperatures. This study includes a literature review to understand the classroom policy in Tanzania, establish links between temperature and learning, and assess temperature retrofit options. Following this, the study presents the results of an experiment to trial a white-paint cool roof against a blue-paint roof and an unpainted control roof. Finally, data analysis predicts the intervention effects over an entire year and the subsequent impact on learning outcomes. The learning outcomes analysis includes a cost-effectiveness analysis using the Learning-Adjusted Years of Schooling (LAYS) metric. Empirical evidence of temperatures inside classrooms in Dar Es Salaam suggests that the temperature often exceeds 40℃. Literature searches indicate that this is the first time classroom air temperatures have been recorded and published for East Africa. The experiment involved using a low-cost retrofit intervention to reduce temperature – by painting the classroom roof blue or white over eight days. Results showed that the White Paint Intervention (WPI) reduced the temperature by around 3.7℃ over the course of the school day and up to a maximum of 5℃. The WPI was roughly twice as effective as the Blue Paint Intervention at reducing interior air temperatures. The WPI results were then modelled to estimate the classroom temperature reduction over a year, based on the assumed 3.5℃ reduction. Finally, using estimates from the existing literature, the learning impact of the intervention was calculated. The results suggest that using the WPI intervention can improve learning by 7.1%, which translates to an estimated 3.2 LAYS per classroom per year, at a cost-effectiveness of 5.3 LAYS per USD100. The paper shows that the impact of high temperatures in classrooms is likely undermining the funding currently channelled to improve learning outcomes in the region. Further, a WPI retrofit intervention is effective at reducing classroom temperatures in Tanzania. Due to climate-change-induced temperature increases, the intervention effectiveness is likely to increase over the coming decades. This paper was submitted as a dissertation in fulfilment of an MSc in Sustainability and Adaptation in the Built Environment at the Centre for Alternative Technology, Machynlleth, Powys (Wales)
Keywords: _r:AddedByZotZen

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Leveraging Existing Technology in Low-Resource Settings to Support Learning: Conceiving and developing implementation plans for schools - Hayat, Amal; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
This document serves as a practical guide for implementers and decision-makers on how available technologies can effectively support teaching and learning in schools worldwide. Drawing on existing evidence of successful EdTech interventions in low-resource settings, particularly within Southeast Asia, it offers guidance on the essential steps in the early phases of EdTech implementation. The report also provides recommendations for transitioning from the initial conception phase to developing a comprehensive implementation plan. Keywords: EdTech implementation guide; low-resource settings; ASEAN; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: Helpdesk Response; _r:AddedByZotZen

Methodology for literature reviews - Haßler, Björn; Adam, Taskeen; Allier-Gagneur, Zoe; Blower, Thomas; Brugha, Meaghan; Damani, Kalifa; Hennessy, Sara; Martin, Kevin; Megha-Bongnkar, Ghislaine; Murphy, Mary; Walker, Hannah; Walker, Hannah (EdTech Hub, 2021)
An output of the EdTEch Hub
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

A Political Economy Analysis Framework for EdTech Evidence Uptake - Pellini, Arnaldo; Nicolai, Susan; Magee, Arran; Sharp, Sam; Wilson, Sam (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

Technology-Supported Personalised Learning: A Rapid Evidence Review - Major, Louis; Francis, Gill A. (EdTech Hub, 2020)
This publication is one part of a series of rapid evidence reviews that has been produced by the EdTech Hub. The purpose of the rapid evidence reviews is to provide education decision-makers with accessible evidence-based summaries of good practice in specific areas of EdTech. They are focused on topics which are particularly relevant in the context of widespread global challenges to formal schooling as a result of COVID-19. All the rapid evidence reviews are available at edtechhub.org.
Keywords: F: Evidence review; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Educational Television: A Rapid Evidence Review - Watson, Joe; McIntyre, Nora (EdTech Hub, 2020)
This Rapid Evidence Review (RER) gives an overview of the recent literature concerning how the use of educational television might support children’s learning in low- and middle-income countries (LMICs). In this review, educational television is defined as television designed with research-based knowledge of how children use and understand television that systematically incorporates academic or social curricula into its content. In low-income contexts, educational television material could be delivered through videos played in schools that are supported by corresponding teacher guidance (e.g. the Mexican school-based T elesecundaria programme), or broadcast on public channels (e.g. the Tanzanian animation, Ubongo Kids). As such, certain educational television projects are capable of functioning even in circumstances where access to formal schooling facilities is restricted. This review therefore provides information that is particularly valuable in the context of the COVID-19 pandemic.
Keywords: L:English UXZJW5DR; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Pakistan Distance-Learning Topic Brief: Primary-level Deaf Children - Lynch, Paul; Kaye, Tom; Terlektsi, Emmanouela (EdTech Hub, 2020)
The Covid-19 crisis has severely impacted the ability of national education actors to provide access to education services for all students.This brief provides guidance and recommendations on how to support the education of deaf children in Pakistan using alternative learning approaches. It presents the rationale for adopting certain teaching and learning strategies when supporting the learning and well-being of deaf children during global uncertainty. Children with deafness and hearing loss are particularly vulnerable during school closures. They are isolated at home and unable to access information as easily as when attending school. This brief presents some of the practices that are reportedly working well for deaf children in different contexts.
Keywords: C:Pakistan; F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

KEY FIGURES: 5th Rwanda Population and Housing Census (PHC) - National Institute of Statistics of Rwanda. (National Institute of Statistics of Rwanda., 2023)
The fifth Population and Housing Census in Rwanda, was conducted in August 2022. The Census operation was coordinated by the National Census Commission. Various census technical and administrative structures have been put in place to ensure a successful census operation.

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Cost-Effective EdTech Paper 2: Good practice - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech in Nigeria: A Rapid Scan. An overview of EdTech policies and interventions in Nigeria with a focus on northern Nigeria - Ramesh Vasudevan, Sharanya; Oyedele, Oluwatomisin (EdTech Hub, 2024)
Commissioned as a Helpdesk request from the FCDO-funded Partnership for Learning for All in Nigeria (PLANE) project, this EdTech Hub rapid scan provides an overview of the EdTech landscape in Nigeria. Given the PLANE programme’s focus on northern Nigeria, this rapid scan also assesses state-level policies and infrastructural challenges in three northern Nigerian states — Jigawa, Kaduna, and Kano. Furthermore, this rapid scan builds on the evidence presented in the previous EdTech Hub rapid scan from 2020, which focused on all states and the situation before the Covid-19 pandemic. Keywords: EdTech; policies; interventions; northern Nigeria; Partnership for Learning for All in Nigeria An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Overview of Emerging Country-Level Response to Providing Educational Continuity Under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
Keywords: ⛔ No DOI found

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Mapping and Analysing Digital Learning Platforms in Latin America and the Caribbean - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in October 2021. The UNICEF team requested a curated list of digital learning platforms in the Latin America and Caribbean (LAC) region and an analysis of a shortlisted series of platforms intending to explore their potential for at-scale implementation and impact. This report does not aim to cover every leading and innovative digital learning platform in the LAC region. Rather, it presents a list of promising platforms and discusses their design and implementation to explore their relevance and potential for at-scale impact. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Deploying an e-Learning Environment in Zanzibar: Feasibility Assessment - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
The Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank (the Bank) approached the EdTech Hub (the Hub) in April 2020 to explore the feasibility of implementing a Virtual Learning Environment (VLE). The Hub was requested to focus primarily on the deployment of a VLE in lower secondary education, and this report consequently focuses primarily on this group. The report is structured in four sections: An introduction to provide the background and guiding principles for the engagement with a short overview of the methodology applied. An analysis of the Zanzibar education system with a particular focus on elements relevant to deploying a VLE. This includes the status of ICT infrastructure, and a summary of the stakeholders who will play a role in using or implementing a VLE. A third section that discusses types of VLEs and content organisation, and their applicability to the Zanzibar ecosystem. A conclusion with recommendations for Zanzibar, including short- and long-term steps. In this collaboration with Zanzibar’s MoEVT, the Hub team sought to understand the purpose of the proposed VLE. Based on discussions and user scenarios, we identified two main education challenges a VLE may help to resolve. In the short term, students cannot go to school during the COVID-19 crisis, but need access to educational content. There is content, but no flexible and versatile platform to disseminate content to all students. In the long term, a mechanism to provide students with access to quality, curriculum-aligned content in school, or remotely, is required.
Keywords: C:Tanzania; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Mapeo y análisis de programas EdTech en América Latina y el Caribe - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
Este documento se elaboró ​​en respuesta a una solicitud de la Oficina Regional de UNICEF para América Latina y el Caribe al Servicio de Asistencia de EdTech Hub en octubre de 2021. El equipo de UNICEF solicitó una lista seleccionada de programas de EdTech en la región de América Latina y el Caribe (ALC) y un análisis de un conjunto de programas preseleccionados con la intención de explorar su potencial para la implementación y el impacto a escala. Este informe no pretende cubrir todos los programas EdTech innovadores en la región de ALC. Más bien, presenta una lista de programas EdTech prometedores y analiza su diseño e implementación con el fin de explorar su relevancia y potencial para lograr un impacto a gran escala. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
Keywords: C:sub-Saharan Africa; _yl:t; dode_eth-src-dode; dode_eth-trf2-dode

O Efeito da COVID-19 na Educação em África e Suas Implicações para a Utilização da Tecnologia Um Inquérito sobre a Experiência e as Opiniões de Educadores e Especialistas em Tecnologia - eLearning Africa; EdTech Hub (2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
Keywords: auto_merged